Optimization of process variables for CO2/CH4 and CO2/N2 binary gas separation using dual-layer hollow fiber mixed-matrix membrane - Muhammad Hamad Zeeshan; Yin Fong Yeong; Thiam Leng Chew (Fuel, 2027)

Self-healing concrete: investigating the synergistic effects of Bacillus subtilis and silica fume - Aayzaz Ahmed; Mirza Aamish Hassan Khan; Milica Vidak Vasić; Mehroz Imtiaz; Arslan Shabir; Tariq Ali; Muhammad Zeeshan Qureshi; Anwar Ahmed (European Journal of Environmental and Civil Engineering, 2026)

Mutation mapping and functional characterization of a missense mutation p.Arg228Cys in ALDH3A2 gene causing Sjögran-Larson syndrome - Muhammad Zeeshan Ali; Samia Sattar; Abdulfatah M. Alayoubi; Shakil Abbas; Mohammed Turki Hussain Alharthi; Alwaleed Fahad H. Altemani; Muhammad Latif; Muzammil Ahmad Khan; Christian Windpassinger (Molecular Biology Reports, 2026)

Bioinformatics-guided vaccine targeting the hemagglutinin protein of avian influenza virus - Sidra Khursheed; Muhammad Zeeshan Ahmed; Saira Khursheed; Zeeshan Mutahir; Noreen Samad (Molecular Genetics and Genomics, 2026)

Diversifying tropical agroforestry: High-value understory crops in rubber and coconut systems - Muhammad Zeeshan Ul Haq; Yaqi Zhao; Muhammad Adnan Ul Haq; Hafiza Amina Iqbal; Waqar Ahmed; Jianfeng Yang; Zhigang Li; Chao Zu; Jie Kang; Weiquan Zheng; Gangqiang Dong; Can Wang (Agricultural Systems, 2026)

Recent advances in protein engineering and synthetic applications of amino acid oxidases - Muhammad Israr; Faiza Basheer; Yi Zhou; Muhammad Zeeshan; Fiza Ali; Shuke Wu (Bioresource Technology, 2026)

Metaheuristic-driven CatBoost models for accurate seepage prediction in heterogeneous earth-fill dams on permeable foundations - Mohamed Kamel Elshaarawy; Muhammad Zeeshan Khursheed; Badee Alshameri; Mohamed Maher Sayed Ahmed (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Boosting low-temperature CO2 methanation through Ni/ZrO2 catalyst-NaA zeolite interplay - Inam Ullah; Syed Musab Ahmed; Hao Lou; Zeeshan Abbasi; Zubair Ahmad; Muhammad Usman; Wenlong Wu; Zhandong Wang (Journal of Environmental Chemical Engineering, 2026)

Reusing end-of-life reverse osmosis membranes: Strategies, challenges, and future perspectives - Zeeshan Arshad; Muhammad Ashraf; Taha Demraoui; Tauqir Ahmad; Muhammad Bilal Asif; Niaz Ali Khan; Mukarram Zubair; Muhammad Irshad Baig; Nisar Ullah; Yasir Abbas; Almotasembellah Abushaban; Nadeem Baig (Desalination, 2026)

Editorial Expression of Concern: Silicon inhibits cadmium uptake by regulating the genes associated with the lignin biosynthetic pathway and plant hormone signal transduction in maize plants - Tariq Shah; Zeeshan Khan; Shah Rukh Khan; Ayesha Imran; Muhammad Asad; Ajaz Ahmad; Parvaiz Ahmad (Environmental Science and Pollution Research, 2026)

Dual-loaded chitosan nanocarriers for sustainable management of Pseudomonas syringae in tomato: A critical narrative review and conceptual synthesis - Zeeshan Ahmad; Urooj Farid; Tauqeer Ahmed Qadri; Sana Azeem Kiani; Arslan Ali; Muhammad Nadeem Hassan; Humaira Yasmin (Physiological and Molecular Plant Pathology, 2026)

Nano-microbial suppression of Tribolium castaneum: Mortality, repellency, and enzyme responses to ginger-derived iron oxide nanoparticles and PGPR strains - Aneela Shaheen; Zeeshan Ahmad; Tauqeer Ahmed Qadri; Sidra Batool; Faheem Ahmad; Muhammad Nadeem Hassan; Humaira Yasmin (Journal of Stored Products Research, 2026)

PFAS associated with dysglycemia and glucose trajectories: a prospective cohort study from the Isomers of C8 Health Project in China - Wen-Qi Yang; Yun-Ting Zhang; Wen-Yu Wang; Haseeb Tufail Moryani; Muhammad Amjad; Zeeshan Mohammed; Xuan Liu; Yan-Xu Chen; Kun Zhao; Chu Chu; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Influence of Temperature and Hydrogen Peroxide Treatment on the Physiochemical and Adsorptive Characteristics of Rice Stalk Biochar for Cadmium Remediation: A Sustainable Solution - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Awais Ahmad; Waed Alahmad; Mohammed S. Alotaibi; Saqer S. Alotaibi; Sajad Ali; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Synergistic role of biochar, AMF, and PGPR in enhancing drought tolerance and productivity of wheat (Triticum aestivum L.) - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Islem Abid; Awais Ahmad; Vusala Ismayilova; Manal Abdulaziz Binobead; Rashid Iqbal (Cereal Research Communications, 2026)

Mapping future agricultural shifts amid water scarcity challenges in the Kabul River Basin using the CLUMondo model - Muhammad Zubair; Shah Fahd; Zeeshan Zafar; Rana Muhammad Zulqarnain; Qaiser Abbas (Advances in Space Research, 2026)

Redox-modulating metallic nanoparticles: mechanistic insights into pharmacological activity and cellular therapeutics - Muhammad Irfan; Umar Zeeshan; Haider; Ali Abbas (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Maximizing weight loss with cagrisema: a systematic review and GRADE-assessed meta-analysis of randomized controlled trials - Bilal Wazir Khan; Syed AsadUllah Agha; Ihsan Qamar; Muhammad Huzaifa Khattak; Amna Rehman; Tayyaba Ikram Qazi; Shahreena Athar Siddiqui; Nafila Zeeshan; Umer Zaryab Khan; Humaira Bibi; Muhammad Faaz Khan; Haris Wazir Khan; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Retraction notice to “Environmental impacts of hazardous waste, and management strategies to reconcile circular economy and eco-sustainability” [Sci. Total Environ. 807 (2022) 150856] - Zhen Zhang; Muhammad Zeeshan Malik; Adnan Khan; Nisar Ali; Sumeet Malik; Muhammad Bilal (Science of The Total Environment, 2026)

Molecular approaches and chemical boundaries in bio-hybrid systems for synergistic remediation of heavy metals and microplastics in groundwater - Abdul Rehman; Sitian Ma; Haowen Xiao; Xiaojun Zheng; Samra Ijaz; Muhammad Zeeshan Gulzar; Muhammad Raza Farooq (Groundwater for Sustainable Development, 2026)

Boiling for micro(nano)plastic mitigation in drinking water: Chemical interactions, potential risks, and research gaps - Abdul Qadeer; Xiang Tu; Muhammad Anis; EH. Ibrahim; Zeeshan Ajmal; Kun Wang; Xia Jiang; Weng Shuhang (Chemical Engineering Journal, 2026)

Environmental KPI Reporting in Ports: Patterns, Gaps, and Opportunities for Systemic Change - Seyedeh Azadeh Alavi-Borazjani; Muhammad Noman Shafique; Zeeshan Arshad (International Journal of Environmental Research, 2026)
Ports play a critical role in global sustainability transitions, yet environmental performance reporting remains fragmented and uneven. This study examines environmental key performance indicator (KPI) reporting practices across twenty-five benchmark ports using a multi-category framework encompassing major environmental dimensions. The analysis reveals that, while most ports have established baseline transparency and compliance with international standards, reporting predominantly focuses on inventory-based and infrastructure-oriented indicators, with limited tracking of outcome-oriented performance metrics such as progress toward emissions reduction targets or reductions in stormwater pollution loads. Performance-based, outcome-oriented, and integrative KPIs remain underrepresented across environmental domains. High-level sustainability commitments are frequently disclosed without systematic progress tracking, and environmental domains are often reported in isolation, limiting holistic planning and comparability. Emerging areas such as climate risk assessment, environmental finance, acoustic management, and regenerative design exhibit particularly low reporting maturity. These findings underscore the need to shift from descriptive, compliance-driven disclosures toward harmonized, integrated KPI frameworks that support performance evaluation, strategic decision-making, and systemic sustainability transformation in the global port sector.

Campylobacter in fresh retail meat: species diversity assessment using a modified filter method compared with ISO 10272:2017 - Lore Heyvaert; Muhammad Zeeshan Zafar; Marie Joossens; Kurt Houf (International Journal of Food Microbiology, 2026)

The dynamic interaction between the semi-circular canyon and a nearby building with a rigid foundation surrounded by flexible bearing layers under incident SH waves - Nasir Abbas; Jebran Saleem; Zeeshan Haider; Darakshan Zahra; Muhammad Lawal Usman (Innovative Infrastructure Solutions, 2026)

Parametric optimization and mechanistic investigation of polyvinyl chloride microplastic degradation via an intensified hydrothermal Fenton reaction - Muhammad Zeeshan Gulzar; Guijian Liu; Muhammad Imran; Muhammad Arif; Samina Irshad; Bisma Sattar; Muhammad Irtaza Sajjad Haider; Huihui Zhou; Balal Yousaf (Journal of Water Process Engineering, 2026)

Removal of perfluoroalkyl substances from drinking water with anion exchange resins and a divinylbenzene sorbent in column experiments - Omamah Ali; Muhammad Zeeshan; Daniel Mahringer; Alexander Kämpfe; Aki Sebastian Ruhl (Journal of Water Process Engineering, 2026)

Thermophoretic heat and mass transfer in magnetohydrodynamic transport of a yeleswarapu fluid driven by metachronal cilia - Muhammad Asif Gondal; Zeeshan Asghar; Muhammad Asif Javed; Muhammad Waris Saeed Khan (Dynamics of Atmospheres and Oceans, 2026)

Arbuscular Mycorrhizal Fungi and Leonardite alter fatty acid and amino acid biosynthesis in sunflower grains - Ghulam Murtaza; Muhammad Usman; Muhammad Rizwan; Sajad Ali; Zeeshan Ahmed; Khairiah Mubarak Alwutayd; Rashid Iqbal (Plant Molecular Biology, 2026)

Removal of congo red dye using agro-titania nanoparticles as biosorbent from aqueous solution - Muhammad Irfan Jalees; Zeeshan Abbas; GulE Hina (Nanotechnology for Environmental Engineering, 2026)

Genome-Wide Identification and In Silico Characterization of the ALKBH Gene Family in Rice (Oryza sativa L.) Under Abiotic Stress Conditions - Shabana Iqbal; Muhammad Naeem; Zeeshan Ali; Muhammad Saqib (Journal of Crop Health, 2026)

A charge conservative finite volume discretization of the Hodgkin-Huxley model - Muhammad Zeeshan Ashraf; Tanel Peets; Kert Tamm (Journal of Computational Neuroscience, 2026)

Enhancement of maize drought resilience using nano-buckminsterfullerenes and plant growth-promoting rhizobacteria: insights into pigment stability, oxidative stress reduction, and yield - Ghulam Murtaza; Muhammad Usman; Najmaldin Ezaldin Hassan; Zeeshan Ahmed; Awais Ahmad; Khairiah Mubarak Alwutayd; Wael Elmenofy; Hassan Mehmood; Rashid Iqbal (Cereal Research Communications, 2026)

Adaptive role of silicon in enhancing crop resilience and yield under stressful environments: A new window for stress management - Ghulam Murtaza; Muhammad Rizwan; Muhammad Usman; Qamar uz Zaman; Zeeshan Ahmed; Rashid Iqbal; Akash Tariq; Gang Deng (Plant Biosystems, 2026)

Geospatial analysis of surface urban heat island dynamics and land use changes in Pakistan using multi-spectral indices - Awais Ali; Bilal Hussain; Muhammad Naveed; Bader Alshehri; Abdul Ghafoor; Zeeshan Zafar; Faisal Sultan Qadri (Advances in Space Research, 2026)

Synergistic application of biochar and mercury-resistant Bacillus cereus enhances phytoremediation efficiency and stress tolerance in sorghum (Sorghum bicolor L.) grown in mercury-contaminated soil - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Rashid Iqbal (Biodegradation, 2026)

Spatiotemporal analysis of climatic and anthropogenic drivers of winter smog in the Indo-Gangetic Plain with a focus on Lahore - Muhammad Zeeshan Ghani; Mujtaba Hassan; Farrukh A. Chishtie; Syeda Saleha Fatim Ali; Syed Waqar Hussain Shah; Ahmad Bilal (Environmental Science and Pollution Research, 2026)

Precision Agriculture Through Green Nanoparticles: Mechanistic Insights into Nutrient Delivery and Enzyme-Targeted Pest Control with Emerging Computational Perspectives - Muhammad Irfan; Hira Altaf; Mishal Naveed; Nadia Zeeshan; Umer Rashid; Amber Afroz (Journal of Soil Science and Plant Nutrition, 2026)

Perfluorooctane sulfonate (PFOS) induces Caspase-8-mediated pyroptosis via GSDMD and GSDME to drive retinal disease: Evidence from epidemiological and experimental studies - Lu-Yin Wu; Li-Xia Liang; Jia-Xin Zhou; Yun-Ting Zhang; Zeeshan Mohammed; Muhammad Amjad; Yang Zhou; Zhi Wang; Guang-Hui Dong; Wen-Wen Bao (Environmental Pollution, 2026)

Advanced Bayesian spatio-temporal frameworks for predicting precipitation at ungauged sites and times - Muhammad Asif Khan; Rangjian Qiu; Muhammad Zubair; Shah Fahd; Zeeshan Zafar (Theoretical and Applied Climatology, 2026)

From haploid inducer to CMS donor: repurposing of CENH3 to create a CMS line in a single step in Brassica napus - Mengyu Lei; Muhammad Zeeshan Mola Bakhsh; Xiaoyu Zhang; Dongli He; Cheng Dai; Chaozhi Ma; Jingxin Tu; Jinxiong Shen; Jing Wen; Tingdong Fu; Bin Yi (Plant Cell Reports, 2026)

Comparative disproportionality signals for methotrexate monotherapy versus methotrexate combined with hydroxychloroquine, leflunomide, or sulfasalazine in rheumatoid arthritis: newly highlighted signals evaluated using drug information safety profiles - Azfar Athar Ishaqui; Khalid Orayj; Zeeshan Ahmed; Salman Ashfaq Ahmad; Sultan M. Alshahrani; Rayah Asiri; Adnan Iqbal; Asaad Ahmed Asaad Khalil; Mohammed Ali Kaddoura; Muhammad Bilal Maqsood (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Plant growth-defense trade-offs regulate phytoremediation efficiency and ecosystem resilience in the contaminated environments - Zeeshan Ahmad; Jiangbo Rao; Muhammad Ilyas; Guorui Xu; Jie Yang (Journal of Environmental Management, 2026)

Techno-economic assessment of field-scale storage for liquid organic hydrogen carriers: dual benefits of energy storage & incremental oil recovery - Zeeshan Tariq; Mutaz AlSubhi; Muhammad Ali; Narendra Kumar; Faisal Alissa; Abdulwahab Ghamdi; Hussein Hoteit (Fuel, 2026)

Model structure and data available for estimation affect uncertainty of genotype-specific parameter estimates - Muhammad Zeeshan Mehmood; Phillip D. Alderman; Romulo P. Lollato; Amanda de Oliveira Silva (European Journal of Agronomy, 2026)

Synergistic photo-assisted AOPs using acid-modified biochar: Enhanced micropollutant levofloxacin degradation in industrial wastewater - Muhammad Irtaza Sajjad Haider; Guijian Liu; Balal Yousaf; Muhammad Arif; Kiran Aziz; Bisma Sattar; Muhammad Zeeshan Gulzar; Hameer Chand; Ruijia Liu (Desalination, 2026)

Role of Nano-Silicon, Nano-Biochar, and Irrigation Strategies in Managing Tellurium Toxicity: Implications for Soil Microbiota, Wheat Yield, and Food Safety - Ghulam Murtaza; Muhammad Usman; Muhammad Azam; Muhammad Rizwan; Zeeshan Ahmed; Rehman Habib; Javed Iqbal; Gamal Awad El-Shaboury; Sajad Ali; Rashid Iqbal (Water, Air, & Soil Pollution, 2026)

Physicochemical Characterization and Molecular Docking of Salicylic Acid-Binding Protein 2 (SABP2) Suggest Drought-Responsive Mechanisms in Tobacco - Mirza Muhammad Ahad Baig; Sarmad Farogh Arshad; Muhammad Asif Saleem; Abdulsmad Baig; Muhammad Mudasir; Zeeshan Ahmad; Taimoor Ali; Abdul Rehman (Journal of Crop Health, 2026)

Retraction Note: Study of variability, combining ability, genetics and association of different yield related traits in rice (Oryza sativa L.) genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Rao Muhammad Ikram; M. Irfan Akram; Ehab I. Taha; Mounir M. Bekhit; Ozhan Simsek; Tolga Izgu; Temoor Ahmed; Javed Iqbal; Rashid Iqbal (Genetic Resources and Crop Evolution, 2026)

Synergistic effects of foliar selenium nanoparticles and aged cellulose-derived biochar on PAH immobilization and spinach health in contaminated soils - Ghulam Murtaza; Muhammad Usman; Muhammad Azam; Zeeshan Ahmed; Sajad Ali; Khairiah Mubarak Alwutayd; Rashid Iqbal (Environmental Geochemistry and Health, 2026)

Role of Acacia bark biochar in the growth of Ocimum basilicum L. under cadmium stress - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Rashid Iqbal; Hossam S. El-Beltagi; Mashael Daghash Alqahtani; Usman Zulfiqar (Biodegradation, 2026)

Combined application of 5-ALA and nitric oxide improves lead detoxification and antioxidant defense in barley - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Wael Elmenofy; Muhammad Aamir Manzoor; Rashid Iqbal (Biodegradation, 2026)

Evaluating the InVEST model to map water ecosystem services in the data-scarce upper Indus basin - Zeeshan Zafar; Shah Fahd; Muhammad Zubair; Rana Muhammad Zulqarnain; Qaiser Abbas (Acta Geophysica, 2026)

Evaluation of Genetic Diversity, Yield, and Its Associated Traits in Rice (Oryza Sativa L.) Genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Abdul Rehman; Shabir Ahmad; Khairiah Mubarak Alwutayd; Fatmah Ahmed Safhi; Javed Iqbal; Rashid Iqbal (Plant Molecular Biology Reporter, 2026)

Biochemical signatures shaping tissue culture success in maize inbred lines - Rimsha Akhtar; Kauser A. Malik; Umer Zeeshan Ijaz; Asma Maqbool; Zohab Asif; Muhammad Irfan (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Co-application Impacts of Silicon and Potassium Fertilizers on Wheat (Triticum Aestivum L.) Growth and Nutritional Attributes in Cadmium-contaminated Soil Under Two Irrigation Regimes - Ghulam Murtaza; Najmaldin Ezaldin Hassan; Muhammad Rizwan; Qamar uz Zaman; Gang Deng; Zeeshan Ahmed; Javed Iqbal; Mohamed S. Elshikh; Humaira Rizwana; Shabir Ahmad; Lala Gurbanova; Rashid Iqbal (Journal of Soil Science and Plant Nutrition, 2026)

Bukiniczia cabulica (Boiss.) Lincz. ameliorate diabetes-induced neuropathy: analgesic, anti-diabetic and anti-neuropathic using enzyme inhibitory, molecular docking and in-vivo studies - Zeeshan Ahmad; Mushtaq Ahmad Mir; Muhammad Shahid; Nasreena Bashir; Alam Zeb; Mehreen Ghufran; Falak Naz; Muhammad Ayaz (Inflammopharmacology, 2026)

Fermentation-based valorization of agro-industrial cereal wastes and by-products - Muhammad Zeeshan Adil; Sebahat Oztekin; Afifa Aziz; Deniz Gunal-Koroglu; Esra Capanoglu; Andres Moreno; Waseem Khalid; Tuba Esatbeyoglu (Trends in Food Science & Technology, 2026)

Remote sensing and multi-method statistical analysis of snow cover variability and hydrological responses in the Upper Indus Basin - Nasir Abbas; Shah Fahd; Ninglian Wang; Muhammad Zubair; Adeel Ahmad Nadeem; Zeeshan Zafar (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Radiative magneto-thermal modeling of tri hybrid nanofluid in blood: A Biomedical intelligent framework for hyperthermia cancer therapy - Zeeshan Ikram Butt; Iftikhar Ahmad; Muhammad Asif Zahoor Raja; Muhammad Shoaib (Journal of Thermal Biology, 2026)

CESAR1 solvent degradation in pilot and laboratory scale - Vanja Buvik; Andreas Grimstvedt; Kai Vernstad; Hanna K. Knuutila; Muhammad Zeeshan; Sundus Akhter; Karen K. Høisæter; Fred Rugenyi; Matthew Campbell (International Journal of Greenhouse Gas Control, 2026)

A comparison of the effect of SMA derivatives on the structural topology and dynamics of two bacteriophage peptides - Nancy C. Rotich; Evelyn A. Okorafor; Indra D. Sahu; Muhammad Zeeshan Shah; Dominik Konkolewicz; Gary A. Lorigan (Chemistry and Physics of Lipids, 2026)

Classification of industrial biobased systems in the EU as basis for sustainability and circularity assessment - Status quo and suggestions for a systematic approach - Muhammad Zeeshan Khan; Gabriele Weber-Blaschke; Omar Hijazi (Bioresource Technology Reports, 2026)

Remediation of Water Contaminated by Toxic Metals with Multi-metal/Co-doped Modified Biochars - Ghulam Murtaza; Muhammad Usman; Zeeshan Ahmed; Muhammad Qasim; Javed Iqbal; Shabir Ahmad; Rashid Iqbal; Lala Gurbanova; Mehdi Rahimi (Water, Air, & Soil Pollution, 2026)

Water Quality deterministic and Probabilistic Health Risks Assessment using Monte Carlo Simulation: Case Study from a Semi-Arid Region - Said Muhammad; Zeeshan Raza; Wajid Ali; Ashfaq Ahmad; Cem Tokatli; Imran Ud Din (Water, Air, & Soil Pollution, 2026)

Integrating Molecular and Ecological Insights for better understanding of Bioremediation Potential of Indigenous Fungal Isolates from the Marble Wastewater - Zeeshan Ahmad; Shujaul Mulk Khan; Adam Khan; Muhammad Ishtiaq Ali; Gulnar Tulindinova; Shahab Ali; Jie Yang (Water, Air, & Soil Pollution, 2026)

Status of insecticide resistance in Spodoptera litura (Lepidoptera: Noctuidae) on cauliflower, Punjab, Pakistan - Dilbar Hussain; Muhammad Sohail Qadir; Muhammad Asrar; Muhammad Saleem; Usama Saleem; Zeeshan Javed; Kanwal Hanif; Arshed Makhdoom Sabir; Ijaz Haider; Muhammad Jawad Saleem; Muhammad Bilal Bin Iqbal (International Journal of Tropical Insect Science, 2026)

Integrating chemical and microbial strategies for heavy metal remediation in contaminated soils: opportunities, challenges, and key factors - Muhammad Zeeshan Basheer; Xuhan Huang; Xiaolin Cai; Yanshan Cui; Murad Muhammad (Environmental Science and Pollution Research, 2026)

Tailoring of Cerium Oxide Nanosheets Having Superior Peroxidase Catalytic Activity for Colorimetric Detection of Hydrogen Peroxide - Mohib Ullah; Muhammad Aslam Khan; Sajid Ali; Asfandyar; Zeeshan Tahir; Muhammad Babar Saeed; Vineet Tirth; Ali Algahtani; Ruqia Nazir; Muslim Khan (Journal of Fluorescence, 2026)

Deciphering auxin-regulated stomatal development: Novel insights into phytochrome-interacting factors, FOUR LIPS, and SNF1-related kinase interactions - Abdul Wakeel Umar; Naveed Ahmad; Hamad Hussain; Muhammad Zeeshan; Ming Xu (Plant Science, 2026)

Associations of particulate matter size fractions and chemical composition with conjunctivitis and eczema: epidemiological evidence from the Pearl River Delta, China - Lu-Yin Wu; Mohammed Zeeshan; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Wen-Wen Bao; Yang Zhou; Muhammad Amjad; Li-Zi Lin; Ru-Qing Liu; Zhi Wang; Guang-Hui Dong (Environmental Research, 2026)

Rainfall threshold analysis for various geological formations in Northeastern Guangdong, China: a physically-based approach - Muhammad Zeeshan Ali; Kejie Chen; Wenfeng Cui; Hai Zhu; Zhiwen Zheng; Wei Zhang; Zhihua Zhou (Natural Hazards, 2026)

Mitigating cadmium-stressed spinach by the synergistic effect of vermicompost and selenium: associated heath risks assessment - Taiba Rauf; Kamran Ashraf; Zeeshan Ahmed; Rabiya Nasir; Muhammad Zeeshan Mansha; Qamar uz Zaman; Ghulam Murtaza; M. Ajmal Ali; Mohamed S. Elshikh; Rashid Iqbal; Lala Gurbanova; Nazim S. Gruda (Environmental Geochemistry and Health, 2026)

Spatial distribution, source characterization, and risk indices of heavy metals pollution in the sediments of the Hindu Kush Lacustrine ecosystem - Said Muhammad; Zeeshan Ahmad; Cem Tokatli; Adnan Khan; Zafar Iqbal; Ashfaq Ahmad (Environmental Geochemistry and Health, 2026)

Future of PARP inhibitors in cancer treatment: overcoming resistance and enhancing efficacy with combination therapies - Muhammad Shoaib; Zeeshan Ahmad Bhutta; Ahsan Javed; Muhammad Nabeel Amjad; Wenzhu Li; Kyung-Chul Choi; Wanxia Pu (Journal of Zhejiang University-SCIENCE B, 2025)

Enhancing CO2/CH4 and CO2/N2 gas separation performance of cellulose triacetate/polysulfone dual-layer hollow fiber mixed matrix membrane encompassing ZIF-90 filler - Muhammad Hamad Zeeshan; Yin Fong Yeong; Thiam Leng Chew (Journal of Environmental Chemical Engineering, 2025)

Tailoring the photoelectrocatalytic properties of ZIF-90 functionalizing with ethylenediamine for CO2 reduction to methanol - Umm E. Ruman; Maizatul Shima Shaharun; Cheng Seong Khe; Cecilia Devi Wilfred; Muhammad Hamad Zeeshan (Fuel, 2025)

Comparative analysis of Apocynum pictum and Apocynum venetum honey: identify with nutritional and health-promoting metabolites - Zeeshan Ali Buttar; Jiyun Ma; Lei Wang; Muhammad Rizwan Shoukat; Wei Ren; Li Jiang; Mohsin Tanveer (Food Chemistry, 2025)

Ontogenetic shifts in alfalfa root distribution and morphology drive soil water depletion and productivity decline in Loess Plateau pastures - Yuxin Hu; Yuhuan Wu; Zeeshan Muhammad; Li Wang; Zikui Wang (CATENA, 2025)

Hybrid ensembled machine learning algorithm for landslide susceptibility assessment and data enhancement via Dual Discriminator Conditional Generative Adversarial Network - Sajid Hussain; Bin Pan; Wajid Hussain; Meer Muhammad Sajjad; Muhammad Ali; Zeeshan Afzal; Rebouh Nazih Yacer; Aqil Tariq (Natural Hazards, 2025)

Heat stress-induced sterility in oilseed crops: a focus on Brassica napus - Muhammad Zeeshan Mola Bakhsh; Muhammad Ikram; Ahmad Ali; Haseeb ur Rehman (Molecular Biology Reports, 2025)

Prevalence of New Delhi Metallo-β-lactamase (blaNDM) gene in a selected population of drug-resistant clinical isolates - Muhammad Shafiq; Aftab Ahmad; Kunza Latif; Muhammad Saeed; Iftikhar Ahmed; Muhammad Zeeshan Hyder (Molecular Biology Reports, 2025)

Flavones-Fortified Biochar Enhances Barley (Hordeum Vulgare L.) Growth and Productivity by Ameliorating Cadmium and Copper Toxicity - Ghulam Murtaza; Muhammad Bilawal Junaid; Faisal Mahmood; Muhammad Usman; Muhammad Azam; Muhammad Rizwan; Alanoud T. Alfagham; Javed Iqbal; Gang Deng; Zeeshan Ahmed; Trobjon Makhkamov; Lala Gurbanova; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Evaluating Soil Reclamation and Growth Enhancing Potential of Various Types of Biochar with Respect To Rice Crop Cultivated in Saline Sodic Soil - Imran Shehzad; Ghulam Sarwar; Abid Mahmood; Kashf Mehmood; Zuhair Hasnain; Muhammad Zeeshan Manzoor; Danish Ibrar; Saqib Bashir; Manzer H. Siddiqui; Saud Alamri; Shahbaz Khan (Journal of Soil Science and Plant Nutrition, 2025)

Dissecting Genetic Variability and Combining Ability for Salt Tolerance in Rice Based on Morpho-Physiological Traits - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq (Journal of Crop Health, 2025)

Development of a wireless vitamin B2 sensor by using flexible and disposable screen-printed electrode modified with g-C3N4 based ternary composite - Muhammad Zeeshan Asghar; Habibulla Imran; Ali shan; Baoyang Lu; Sooman Lim (Analytica Chimica Acta, 2025)

Optimizing aquaculture sustainability: Microalgae-based co-culture systems for aquaculture wastewater treatment and pollution reduction - Javaeria Maqsood Gill; Syed Makhdoom Hussain; Shafaqat Ali; Ameer Fawad Zahoor; Abdulrahman Alasmari; Muhammad Munir; Eman Naeem; Muhammad Amjad; Zeeshan Yousaf; Muhammad Faisal (Algal Research, 2025)

Cytoplasmic male sterility: Sterility induction, fertility restoration and gene-for-gene interaction of CMS/Rf genes - Ahmad Ali; Muhammad Zeeshan Mola Bakhsh; Shipeng Li; Xiaoyu Zhang; Jinxing Tu; Bin Yi (Plant Science, 2025)

From roots to resilience: Strigolactones for boosting crop resilience and productivity under stressful environments - Zeeshan Ahmed; Dongwei Gui; Ghulam Murtaza; Muhammad Shareef; Akash Tariq (Journal of Environmental Management, 2025)

Retraction notice to “Synergistic effect of silicon and arbuscular mycorrhizal fungi reduces cadmium accumulation by regulating hormonal transduction and lignin accumulation in maize” [Chemosphere 346, January 2024, 140507] - ShahRukh Khan; Zubair Ahmad; Zeeshan Khan; Umair Khan; Muhammad Asad; Tariq Shah (Chemosphere, 2025)

Retraction notice to “Strigolactone decreases cadmium concentrations by regulating cadmium localization and glyoxalase defense system: Effects on nodules organic acids and soybean yield” [Chemosphere 335, September 2023, 139028] - Tariq Shah; Muhammad Asad; Zeeshan Khan; Khadija Amjad; Abdulaziz Abdullah Alsahli; Roberto D'amato (Chemosphere, 2025)

Continuous cropping obstacles in medicinal plants: Driven by soil microbial communities and root exudates. A review - Muhammad Zeeshan Ul Haq; Zeqi Bai; Guangtao Gu; Ya Liu; Dongmei Yang; Huageng Yang; Jing Yu; Yougen Wu (Plant Science, 2025)

Selenium mitigates boron toxicity in Nicotiana tabacum via altering root anatomy, accumulation of boron, biochemical and physiological aspects - Ghulam Murtaza; Zeeshan Ahmed; Gang Deng; Sohail Akhtar; Muhammad Rizwan; Muhammad Usman; Mona S. Alwahibi; Humaira Rizwana; Tolga İzgü; Özhan Şimşek; Rashid Iqbal; Faisal Zulfiqar (Plant Biosystems, 2025)

Prevalence and integrated risk assessment of antibiotics from River Chenab Pakistan; human and ecotoxicological prospectives - Aqeel Mahmood; Hafiz Muhammad Irfan; Alamgeer; Zeeshan Javed; Adeel Mahmood (Science of The Total Environment, 2025)

Integrated PSInSAR and SBAS-InSAR analysis for landslide detection and monitoring - Sajid Hussain; Bin Pan; Wajid Hussain; Meer Muhammad Sajjad; Muhammad Ali; Zeeshan Afzal; M. Abdullah-Al-Wadud; Aqil Tariq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

A multi-compartment physiologically based pharmacokinetic (PBPK) model coupled with Fourier-ARIMA (auto regressive integrated moving average) for estimation and prediction of polychlorinated biphenyls (PCB) concentration in tuna - Sadia Noon Oishe; Muhammad Zeeshan Jamil; Yoshiki Nishi (Aquatic Toxicology, 2025)

Enhanced you only look once v5s crack detection and classification technique by optimizing transformer architecture and convolutional complexity - Umar Ali; Muhammad Arshad Shehzad Hassan; Asim Khan; Muhammad Zeeshan Khan; Maryam Shahzadi (Innovative Infrastructure Solutions, 2025)

Co-existence of Glomus versiforme and nitrile butadiene rubber has an antagonistic effect on soil greenhouse gas emissions - Juan Yang; Xiaoyuan Chi; Xinxin Zhang; Na Chen; Lijuan Pan; Jing Xu; Xiangzhen Yin; Xiao Jiang; Xuhong Zhao; Muhammad Zeeshan; Xunbo Zhou; Jinghua Huang; et al. (Applied Soil Ecology, 2025)

Green chemistry for prostate health: exploring nature’s toolbox against cancer, inflammation, and hyperplasia - Muavia Sarwar; Hafiz Muhammad Irfan; Alamgeer; Zeeshan Jabbar; Mulazim Hussain Asim; Muhammad Sajjad Hassan; Shoaib Nawaz (Molecular Diversity, 2025)

Endophytic Meyerozyma guilliermondii augmented growth attributes and metabolite production in Triticum aestivum under salinity stress - Zeeshan Khan; Muhammad Irshad; Anwar Hussain; Arshad Iqbal; Zamarud Shah; Waheed Murad; Eman R. Elsharkawy; Muhammad Nafees (Folia Microbiologica, 2025)

Microplastic contamination in agricultural soils from mulch films and organic amendments: Transformation mechanism, soil-Biota toxicity, and future perspectives - Bisma Sattar; Guijian Liu; Balal Yousaf; Muhammad Arif; Muhammad Zeeshan Gulzar; Muhammad Irtaza Sajjad Haider; Rabia Safeer; Samra Ijaz; Muhammad Awais Haider; Kiran Aziz (Waste Management, 2025)

Antifungal activity and potential inhibition mechanism of 4-(diethylamino)salicylaldehyde against Rhizoctonia solani - Sishi Huang; Xiaoyue Yang; Jing Zhao; Muhammad Zeeshan; Chunjuan Wang; Desong Yang; Xiaoqiang Han; Guoqiang Zhang (Pesticide Biochemistry and Physiology, 2025)

Intensifying the charge transfer on N–(CxNx+1) catalysts system: A cutting–edge approach for sunlight driven hydrogen production† - Ejaz Hussain; Muhammad Jalil; Javeria Mansab; Muhammad Zeeshan Abid; Shahid Iqbal; Abeer Hashem; Amal M. Al-Mohaimeed; Elsayed Fathi Abd_Allah; Khezina Rafiq (Fuel, 2025)

Recent advancements in chemometrics based non-destructive analytical techniques for rapid detection of adulterants in milk and dairy products – A review - Rui Xu; Muhammad Zeeshan Adil; Sidra Jabeen; Khansa; Mahwish Tanveer; Sadia Younis; Bakhtawar Shafique; Long Li (Food Control, 2025)

Effect of MXenes, nZVI and Acacia-wood Biochar Treatments on Bioavailability Pb and Fractions in Calcareous-polluted Soils - Ghulam Murtaza; Najmaldin Ezaldin Hassan; Muhammad Usman; Gang Deng; Zeeshan Ahmed; Javed Iqbal; Mohamed S. Elshikh; Humaira Rizwana; Rashid Iqbal (Water, Air, & Soil Pollution, 2025)

Severe rainfall-induced landslides in Pingyuan County, Guangdong, China, in June 2024 - Wei Zhang; Muhammad Zeeshan Ali; Wenfeng Cui; Chuangeng Sun; Zhiwen Zheng; Kejie Chen (Landslides, 2025)

Review on crack detection in civil infrastructure using structural health monitoring and machine learning techniques - Muhammad Zeeshan Khan; Maryam Shahzadi; Asim Khan; Umar Ali; Muhammad Arshad Shehzad Hassan; Majid Hussain (Innovative Infrastructure Solutions, 2025)

Therapeutic applications of quercetin-metallic complexes: a review - Nasreen Ramzan; Huma butt; Muhammad Azeem; Muhammad Hanif; Khalid Mahmood; Sadia Rehman; Dure shahwar; Muhammad Zeeshan; Qurat-ul-Ain Ahmad; Mehreen Jabeen (BioMetals, 2025)

Genetic analysis in a consanguineous MCPH family revealed a refinement of the MCPH12 locus and a founder effect of the recurrent CDK6 variant [c.589G>A, p.(Ala197Thr)] in the Pakistani population - Muzammil Ahmad Khan; Jasmin Blatterer; Markus Kuster; Lukas Kaufmann; Peter M. Kroisel; John B. Vincent; Muhammad Zubair; Muhammad Muzammal; Nisar Ahmad; Shakil Abbas; Wasim Shah; Muhammad Zeeshan Ali; et al. (Journal of Genetics, 2025)

Glutathione's role in mitigating cadmium stress in Pogostemon cablin: Insights from combined transcriptomic and metabolomic approaches - Zhineng Fu; Yanqiang Yao; Muhammad Zeeshan Ul Haq; Ya Liu; Dongmei Yang; Huageng Yang; Yougen Wu (Journal of Hazardous Materials, 2025)

Distribution modelling and future prediction of a threatened species - Heracleum candicans Wall. ex DC.; Within the framework of biotic and abiotic interactions - Jawad Hussain; Shujaul Mulk Khan; Muhammad Shakeel Khan; Zafeer Saqib; Abdullah; Zeeshan Ahmad; Maria Shah; Nazir Mohammad; Zareena Batool; Amir Sohail; Jie Liu (Journal of Environmental Management, 2025)

Evaluating the AgMIP calibration protocol for crop models; case study and new diagnostic tests - Daniel Wallach; Kwang Soo Kim; Shinwoo Hyun; Samuel Buis; Peter Thorburn; Henrike Mielenz; Sabine Julia Seidel; Phillip D. Alderman; Benjamin Dumont; Mohammad Hassan Fallah; Gerrit Hoogenboom; Eric Justes; et al. (European Journal of Agronomy, 2025)

Synergistic Effects of 5-Ureidohydantoin, Rhizobacteria and Non-wood-Based Biochar on Barley Productivity Under Drought and Multiple Toxic Metals Stress - Ghulam Murtaza; Muhammad Usman; Muhammad Azam; Abdul Razzaq; Iram Saba; Gang Deng; Zeeshan Ahmed; Abdel-Rhman Z. Gaafar; Trobjon Makhkamov; Lala Gurbanova; Rashid Iqbal (Current Microbiology, 2025)

Metal organic frameworks embedded polymeric membranes: A comprehensive review on application in water purification and seawater desalination - Emre Cevik; Arfa Iqbal; Ayyaz Mustafa; Talal F. Qahtan; Muhammad Zeeshan; Omer Isik (Journal of Environmental Chemical Engineering, 2025)

Fe-Modified Biochar Improves Tobacco Productivity by Promoting Root Growth, Plant Biochemical Traits and Nicotine Level: A Three Years Field Study - Ghulam Murtaza; Muhammad Usman; Qamar uz Zaman; Zeeshan Ahmed; Mona S Alwahibi; Humaira Rizwana; Javed Iqbal; Muhammad Qasim; Rashid Iqbal; Gang Deng (Journal of Soil Science and Plant Nutrition, 2025)

Organic matter and microplastics nexus: A comprehensive understanding of the synergistic impact on soil health - Samra Ijaz; Guijian Liu; Abdul Rehman; Muhammad Irtaza Sajjad Haider; Rabia Safeer; Bisma Sattar; Muhammad Zeeshan Gulzar; Sofia Nosheen; Balal Yousaf (Science of The Total Environment, 2025)

Hydrothermal integrated chemical treatment of microplastics for efficient degradation: Mechanistic insight and degradation behavior - Muhammad Zeeshan Gulzar; Guijian Liu; Balal Yousaf; Muhammad Imran; Muhammad Arif; Muhammad Nauman; Muhammad Irtaza Sajjad Haider; Bisma Sattar; Rabia Safeer; Samra Ijaz; Ruijia Liu (Journal of Water Process Engineering, 2025)

Assessing solar energy potential and CO2 reduction through GIS-based spatial analysis for optimal site selection of photovoltaic systems in Jeddah, Saudi Arabia - Farnaz; Muhammad Zeeshan Ali; Nasim Ullah; Vojtech Blazek; Stanislav Misak (Remote Sensing Applications: Society and Environment, 2025)

Protective Effects of Multiple-Chemical Engineered Biochar On Hormonal Signalling, Antioxidant Pathways and Secondary Metabolites in Lavender Exposed to Chromium and Fluoride Toxicity - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Qamar uz Zaman; Gang Deng; Suiyun Chen; Mona S. Alwahibi; Humaira Rizwana; Javed Iqbal; Shabir Ahmad; Rashid Iqbal (Journal of Crop Health, 2025)

Synthetic bacterial communities regulate polyamine metabolism and genes encoding antioxidant defense system to enhance arsenic tolerance of rice - Hamad Khan; Zeeshan Khan; Ishmal Eman; Ijaz Ahmad; Tariq Shah; Guoping Wang; Lu Feng; Abdullah A. Alarfaj; Sulaiman Ali Alharbi; Muhammad Javed Ansari (South African Journal of Botany, 2025)

Silent threats of lead-based paints in toys and households to children’s health and development - Muhammad Ubaid Ali; Muhammad Zeeshan Gulzar; Bisma Sattar; Sajeela Sehar; Qumber Abbas; Muhammad Adnan; Jingwei Sun; Zhuanxi Luo; Gongren Hu; Ruilian Yu; Ming Hung Wong (Journal of Hazardous Materials, 2025)

Retraction notice to “Mycorrhizosphere bacteria inhibit greenhouse gas emissions from microplastics contaminated soil by regulating soil enzyme activities and microbial community structure” [J. Environ. Manag. 356 (2024) 120673] - Zeeshan Khan; Tariq Shah; Ghulam Haider; Fazal Adnan; Zeshan Sheikh; Mohamed A. El-Sheikh; Muhammad Faraz Bhatti; Parvaiz Ahmad (Journal of Environmental Management, 2025)

Retraction notice to “Alleviation of microplastic toxicity in soybean by arbuscular mycorrhizal fungi: Regulating glyoxalase system and root nodule organic acid” [J. Environ. Manag. 349 (2024) 119377] - Zeeshan Khan; Tariq Shah; Muhammad Asad; Khadija Amjad; Abdulaziz Abdullah Alsahli; Parvaiz Ahmad (Journal of Environmental Management, 2025)

Retraction notice to “Straw incorporation into microplastic-contaminated soil can reduce greenhouse gas emissions by enhancing soil enzyme activities and microbial community structure” [J. Environ. Manag. 351 (2024) 119616] - Tariq Shah; Zeeshan Khan; Muhammad Asad; Ayesha Imran; Muhammad Bilal Khan Niazi; Raf Dewil; Ajaz Ahmad; Parvaiz Ahmad (Journal of Environmental Management, 2025)

Compositions and concentrations of dissolved organic matter, selected elements and anions in German drinking waters - Muhammad Zeeshan; Vanessa Ingold; Leon Saal; Christian Höra; Alexander Kämpfe; Aki Sebastian Ruhl (Journal of Environmental Management, 2025)

Enhanced microwave absorption and improved broadband with synergistic effect of nest like self-assembly of CoFe2O4/Co3O4 heterostructured composites - M. Zeeshan Ashfaq; Aamna Ashfaq; Xingxing Cheng; Hongyu Gong; Adil Saleem; Rashid Iqbal; Muhammad Sajjad; Junbin Lu; M. Mamoor; Muhammad K. Majeed (Chemical Engineering Journal, 2025)

RETRACTED ARTICLE: Study of variability, combining ability, genetics and association of different yield related traits in rice (Oryza sativa L.) genotypes - Zeeshan Ali; Muhammad Naeem; Iqra Rafiq; Rao Muhammad Ikram; M. Irfan Akram; Ehab I. Taha; Mounir M. Bekhit; Ozhan Simsek; Tolga Izgu; Temoor Ahmed; Javed Iqbal; Rashid Iqbal (Genetic Resources and Crop Evolution, 2025)

Liver transcriptome analysis reveals the molecular response to hibernation challenge in the Chinese soft-shelled turtle (Pelodiscus sinensis) - Muhammad Shahid Iqbal; Xiaoqi Ai; Qingjun Zhu; Ijaz Khan; Zeeshan Ali; Tian Lan; Li Ding; Meiling Hong (Frontiers in Marine Science, 2025)
Hibernation is a physiological strategy animals use to survive in hostile environments with extreme temperature challenges and food scarcity. During this state, significant changes occur in metabolism and cellular function, with numerous stress response pathways recalibrated to survive physiological challenges that could otherwise be fatal. Numerous studies were performed to explain the molecular mechanisms of mammalian hibernation, but detailed analyses remain scarce in reptiles. Given the limited understanding of the mechanisms regulating hibernation, we performed a comprehensive analysis of liver gene expression in the Chinese softshell turtle ( Pelodiscus sinensis ) comparing summer active (SA), hibernation (H), and early arousal (EA) states using RNA-sequencing. A total of 435 million high-quality reads were generated, identifying 3,508, 3,607, and 2,993 differentially expressed genes (DEGs) in the SA vs. H, H vs. EA, and EA vs. SA respectively. Gene ontology analysis revealed a shift in metabolic fuel utilization, with the down-regulation of metabolic and cellular processes during hibernation, reflecting a conserved strategy for energy conservation. The transition from hibernation to early arousal was marked by up-regulation of immune-related genes (e.g., CXCL12, ITGA4, PIGR) and endocrine regulators (e.g., CDKN1A, DLL4, IGF1R), facilitating metabolic recovery and cellular protection. Besides, we observed dynamic changes in carbohydrate and lipid metabolism, with down-regulation of hexokinase 2 (HK2) and glucose transporters during hibernation, and up-regulation of lipid metabolism genes (LSS, GPLD1) to support membrane integrity and signaling. Our findings provide insights into the molecular mechanisms underlying hibernation and arousal in ectotherms, with implications for understanding metabolic adaptations, immune regulation, and stress responses in extreme conditions.

Mycorrhizopshere bacteria alleviated arsenic toxicity by regulating organic acids, glyoxalase defense system, and metal transporters in soybean plants - Zeeshan Khan; Shahrukh Khan; Mansour I. Almansour; Muhammad Asad; Mohammad Javed Ansari; Hamad Khan; Ijaz Ahmad (South African Journal of Botany, 2025)

Biohydrogen and biomethane production from biomass gasification: Compositional analysis, recent advancements, challenges, and prospects - Ahmad Naquash; Zeeshan Hameed; Muhammad Abdul Qyyum; Zakir Khan; Ala’a H. Al-Muhtaseb; Amjad Riaz; Moonyong Lee (Process Safety and Environmental Protection, 2025)

Modified approach to estimate effective porosity using density and neutron logging data in conventional and unconventional reservoirs - Muhammad Abid; Jing Ba; Uti Ikitsombika Markus; Zeeshan Tariq; Syed Haroon Ali (Journal of Applied Geophysics, 2025)

Catalytic charge synergy on Ni/Sr@rTiO2 system to promote hydrogen evolution for the implementation of green energy technologies - Ejaz Hussain; Sidra Khan; Muhammad Jalil; Muhammad Zeeshan Abid; Abdul Rauf; Nagina Naveed Riaz; Abeer Hashem; Ajay Kumar; Elsayed Fathi Abd_Allah; Khezina Rafiq (Fuel, 2025)

Key function mechanism of Na3PO4-modified NaX for enhanced performance and stability in side chain alkylation of toluene with methanol: DFT and experimental perspectives - Faraz Ahmad; Yueli Wen; Muhammad Zeeshan; Bin Wang; Awais Ashraf; Bai Hui; Zheng Cui; Chengda Li; Samia Kausar; Wei Huang (Fuel, 2025)

Amine-functionalized organically modified silica for the effective adsorption of Chlorpyrifos and Triazophos Residues from Orange juice - Muhammad Hayat; Suryyia Manzoor; Nadeem Raza; Hina Raza; Ayesha Javid; Zeeshan Ali; Muhammad Imran Khan; Faisal K. Algethami; Najla AlMasoud; Taghrid S. Alomar (Food Chemistry, 2025)

A comprehensive overview on the occurrence and removal of per- and polyfluoroalkyl substances through adsorption and biodegradation - Muhammad Zeeshan; Shamas Tabraiz; Safeerul Islam Hashmi; Arfa Iqbal; Daniel Dittmann; Zohaib Abbas; Cecilia L. MacLeod; Aki Sebastian Ruhl (Bioresource Technology Reports, 2025)

A novel numerical approach for the assessment of the seepage failure, predictive modelling of seepage through non-homogenous earth-fill dams resting on pervious foundations using artificial neural networks - Muhammad Zeeshan Khursheed; Badee Alshameri; Waqas Hassan; Lokmane Abdeldjouad (Modeling Earth Systems and Environment, 2025)

Evaluation of Genotype × Environment Interaction and Yield Stability of Cotton (Gossypium hirsutum L) Genotypes Under Heat Stress Conditions - Iram Sharif; Saba Aleem; Jamshaid Ali Junaid; Muqadas Aleem; Khazina Jamshaid; Huma Saleem; Muhammad Rizwan; Shahid Munir Chohan; Saqib Sohail; Saba Akram; Muhammad Zeeshan; Ghulam Sarwar (Journal of Crop Health, 2025)

Effects of Tribulus terrestris extract and 17 α-methyl testosterone on masculinization, growth, economic efficiency and health assessment of Nile tilapia (Oreochromis niloticus) - Habib Ul Hassan; Amjad Ali; Basim S. A. Al Sulivany; Muhammad Kabir; Roohi Kanwal; Mohammad Z. Ahmed; Rizwana Abdul Ghaffar; Meer Zeeshan Ijaz; Naseem Rafiq; Mary Mahwish; Mohammad Abdul Momin Siddique (Aquaculture International, 2025)

Monitoring and biochemical characterization of resistance against commonly used insecticides in cotton jassid, Amrasca biguttula (Ishida) from Punjab, Pakistan - Sikandar Hussain; Shoaib Freed; Afifa Naeem; Muhammad Sheraz Shah; Muhammad Zeeshan Nazar; Muhammad Waqas Sumra (International Journal of Tropical Insect Science, 2025)

Unveiling the surface potential and selectivity of Ti3C2Tx/rGO adsorbents for arsenic removal from water system - Muhammad Zeeshan Abid; Khezina Rafiq; Aqsa Khan Buzdar; Muhammad Zaryab Waleed; Ejaz Hussain (Journal of Cleaner Production, 2025)

Synergistic effect of biochar and intercropping on lead phytoavailability in the rhizosphere of a vegetable-grass system - Muhammad Rizwan; Ghulam Murtaza; Zeeshan Ahmed; Qimei Lin; Xuejiao Chen; Imran Khan; Hamada Abdelrahman; Vasileios Antoniadis; Esmat F. Ali; Sang Soo Lee; Lijian Leng; Sabry M. Shaheen; et al. (Science of The Total Environment, 2024)

Mechanisms of selectivity for azadirachtin in honeybees (Apis cerana): A new strategy for avoiding thiamethoxam ingestion - Hao Wu; Sheng-nan Li; Rui-quan Hou; Peng-rui Du; Kun-yu Zhao; Muhammad Zeeshan; Han-hong Xu; Zhi-xiang Zhang; Pei-wen Zhang (Pesticide Biochemistry and Physiology, 2024)

Spatial distribution, ecological and human health risks of potentially toxic elements (PTEs) in river Ravi, Pakistan: A comprehensive study - Muhammad Irfan Ahamad; Adnanul Rehman; Muhammad Sajid Mehmood; Shakeel Mahmood; Zeeshan Zafar; Heli Lu; Wanfu Feng; Siqi Lu (Environmental Research, 2024)

Socio-economic benefits and policy implications of generating sustainable energy from municipal solid waste in Pakistan - Waqas Ahmad; Muhammad Hassan; Shah Fahad Bin Masud; Muhammad Saad Amjad; Fatin Samara; Zeshan; Mustafa Anwar; Muhammad Zeeshan Rafique; Tahir Nawaz (Energy and Climate Change, 2024)

Elucidating the bioremediation potential of laccase and peroxidase enzymes from Bacillus ligniniphilus L1 in antibiotic degradation: A computationally guided study - Muhammad Zohaib Nawaz; Hafiz Rameez Khalid; Muhammad Usman Mirza; Lingxia Xu; Syed Zeeshan Haider; Khalid A. Al-Ghanim; Damià Barceló; Daochen Zhu (Bioresource Technology, 2024)

CRISPR-Cas9 based molecular breeding in crop plants: a review - Muhammad Ikram; Abdul Rauf; Muhammad Junaid Rao; Muhammad Faizan Khurram Maqsood; Muhammad Zeeshan Mola Bakhsh; Maaz Ullah; Maria Batool; Muhammad Mehran; Maryam Tahira (Molecular Biology Reports, 2024)

Recovery Efficacy of Differentially Applied Nitrogen Regulates the Metabolism Coupled Physiological Phenotyping of Cotton on Leaching Prone Sandy Soil of Desert - Muhammad Shareef; Fanjiang Zeng; Gui Dongwei; Zeeshan Ahmed; Muhammad Waqas; Hassan Iqbal; Bo Zhang; Muhammad Waseem (Journal of Soil Science and Plant Nutrition, 2024)

Efficacy and safety of ticagrelor monotherapy following a brief DAPT vs. prolonged 12-month DAPT in ACS patients post-PCI: a meta-analysis of RCTs - Usama Qamar; Farhan Naeem; Muhammad Talha Maqsood; Maleeka Zamurad Khan; Zeeshan Imtiaz; Fatima Saeed; Neelesh Gupta; Fnu Zafarullah Brohi; Celestine Mkpozi; Yasar Sattar (European Journal of Clinical Pharmacology, 2024)

Investigations of aerosol types classification and PM2.5 concentrations: A case study of two major cities in Pakistan - Muhammad Zeeshan; Khan Alam (Air Quality, Atmosphere & Health, 2024)

A cutting–edge approach to remove arsenic contents from ground water via sulfur doped copper ferrites (S–CuFe2O4) † - Ejaz Hussain; Aqsa Khan Buzdar; Muhammad Zeeshan Abid; Abdul Rauf; Khezina Rafiq (Journal of Environmental Management, 2024)

Arthropods in soil reclamation and bioremediation: Functional roles, mechanisms and future perspective - Khurram Shehzad; Shuxin Tu; Muhammad Zeeshan Majeed; Bo Lei; Jie Zhang (Journal of Environmental Management, 2024)

Synthesis of green magnetic hybrid adsorbents and their application for reactive red methyl 4 BL dye removal - Sadaf Gillani; Ruba Munir; Khuram Ali; Muhammad Zeeshan Bashir; Umme Habibah Siddiqua; Saima Noreen (Clean Technologies and Environmental Policy, 2024)

Evaluating the biological activity of rolB-transgenic Nicotiana tabacum plants using phytochemical and pharmacological approaches - Afshan Anwar; Shabana Haneef; Hammad Ismail; Muhammad Zeeshan Bhatti; Nazif Ullah; Iram Murtaza; Bushra Mirza (Plant Biosystems, 2024)

An Adaptive Approach in Polymer-Drug Nanoparticle Engineering using Slanted Electrohydrodynamic Needles and Horizontal Spraying Planes - Amna Ali; Saman Zafar; Manoochehr Rasekh; Tahir Ali Chohan; Francesca Pisapia; Neenu Singh; Omar Qutachi; Muhammad Sohail Arshad; Zeeshan Ahmad (AAPS PharmSciTech, 2024)

Agricultural productivity and rural poverty in China: The impact of land reforms - Irfan Ullah; Vishal Dagar; Tauhidul Islam Tanin; Alam Rehman; Muhammad Zeeshan (Journal of Cleaner Production, 2024)

Intercalation of GO-Ag nanoparticles in cellulose acetate nanofiltration mixed matrix membrane for efficient removal of chromium and cobalt ions from wastewater - Muhammad Hamad Zeeshan; Umm E. Ruman; Muhammad Shafiq; Sharjeel Waqas; Aneela Sabir (Journal of Environmental Chemical Engineering, 2024)

Flexible MXenes for printing energy storage devices - Iftikhar Hussain; Onkar Jaywant Kewate; Sumanta Sahoo; Sikandar Aftab; P. Rosaiah; Muhammad Ahmad; Muhammad Bilal Hanif; Wail Al Zoubi; Zeeshan Ajmal; Waqas Ul Arifeen; Mohd Zahid Ansari; Bhargav Akkinepally; et al. (Chemical Engineering Journal, 2024)

High-resolution landslide mapping and susceptibility assessment: Landslide temporal variations and vegetation recovery - Muhammad Zeeshan Ali; Kejie Chen; Muhammad Shafique; Muhammad Adnan; Zhiwen Zheng; Wei Zhang; Zhanhui Qing (Advances in Space Research, 2024)

The pH-dependent role of different manganese oxides in the fate of arsenic during microbial reduction of arsenate-bearing goethite - Xiaotong Liu; Xiaolin Cai; Naiyi Yin; Xuhan Huang; Pengfei Wang; Muhammad Zeeshan Basheer; Chuanfang Fan; Xuhui Chang; Zhengyi Hu; Guoxin Sun; Yanshan Cui (Water Research, 2024)

Azotobacter Modulate Nitrogen Assimilation, Sustain Light Harvesting Efficiency and Photosynthetic Performance of Maize Cultivar in a Saline Soil - Komal Nida; Zamin Shaheed Siddiqui; Manzer H. Siddiqui; Zeeshan Ahmed Salman; Muhammad Umar (Journal of Soil Science and Plant Nutrition, 2024)

Non-linear ground deformation detection and monitoring using time series InSAR along the coastal urban areas of Pakistan - Sajid Hussain; Bin Pan; Zeeshan Afzal; Wajid Hussain; Yin Jianhui; Meer Muhammad Sajjad; Muhammad Ali (Environmental Science and Pollution Research, 2024)

Sustainable Central Asia: Impact of fintech, natural resources, renewable energy, and financial inclusion to combat environmental degradation and achieving sustainable development goals - Yu Jie; Zeeshan Rasool; Abdelmohsen A. Nassani; Suchira Mattayaphutron; Muhammad Murad (Resources Policy, 2024)

Innovative strategy for the effective utilization of coal waste slag in the Fenton-like process for the degradation of trichloroethylene - Mudassir Habib; Tehreem Ayaz; Meesam Ali; Muhammad Zeeshan; Xianxian Sheng; Rongbing Fu; Siraj Ullah; Shuguang Lyu (Journal of Environmental Management, 2024)

Re-examination of effects of pairing gaps on charge-changing transitions - Jameel-Un Nabi; Muhammad Tahir; Asim Ullah; Zeeshan Khan; Muhammad Aswad Ali Shah (Advances in Space Research, 2024)

Physicochemical properties and performance of non-woody derived biochars for the sustainable removal of aquatic pollutants: A systematic review - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Rashid Iqbal; Faisal Zulfiqar; Akash Tariq; Allah Ditta (Chemosphere, 2024)

Numerical investigation of vortex-induced vibrations (VIV) of a rotating cylinder in in-line and cross-flow directions subjected to oscillatory flow - Ubaid Ur Rehman; Adnan Munir; Niaz Bahadur Khan; Ming Zhao; Muhammad Kashif; Mohammad S. Islam; Zeeshan Saeed; Mian Ashfaq Ali (Ocean Engineering, 2024)

Particulate and gaseous air pollutants exceed WHO guideline values and have the potential to damage human health in Faisalabad, Metropolitan, Pakistan - Nukshab Zeeshan; Ghulam Murtaza; Hamaad Raza Ahmad; Abdul Nasir Awan; Muhammad Shahbaz; Peter Freer-Smith (Environmental Monitoring and Assessment, 2024)
First-ever measurements of particulate matter (PM 2.5 , PM 10 , and TSP) along with gaseous pollutants (CO, NO 2 , and SO 2 ) were performed from June 2019 to April 2020 in Faisalabad, Metropolitan, Pakistan, to assess their seasonal variations; Summer 2019, Autumn 2019, Winter 2019–2020, and Spring 2020. Pollutant measurements were carried out at 30 locations with a 3-km grid distance from the Sitara Chemical Industry in District Faisalabad to Bhianwala, Sargodha Road, Tehsil Lalian, District Chiniot. ArcGIS 10.8 was used to interpolate pollutant concentrations using the inverse distance weightage method. PM 2.5 , PM 10 , and TSP concentrations were highest in summer, and lowest in autumn or winter. CO, NO 2 , and SO 2 concentrations were highest in summer or spring and lowest in winter. Seasonal average NO 2 and SO 2 concentrations exceeded WHO annual air quality guide values. For all 4 seasons, some sites had better air quality than others. Even in these cleaner sites air quality index (AQI) was unhealthy for sensitive groups and the less good sites showed Very critical AQI (> 500). Dust-bound carbon and sulfur contents were higher in spring (64 mg g −1 ) and summer (1.17 mg g −1 ) and lower in autumn (55 mg g −1 ) and winter (1.08 mg g −1 ). Venous blood analysis of 20 individuals showed cadmium and lead concentrations higher than WHO permissible limits. Those individuals exposed to direct roadside pollution for longer periods because of their occupation tended to show higher Pb and Cd blood concentrations. It is concluded that air quality along the roadside is extremely poor and potentially damaging to the health of exposed workers. Graphical abstract

Local surface warming assessment in response to vegetation shifts over arid lands of Central Asia (2001−2020) - Sikandar Ali; Akash Tariq; Patient Mindje Kayumba; Fanjiang Zeng; Zeeshan Ahmed; Muhammad Azmat; Richard Mind'je; Tianju Zhang (Science of The Total Environment, 2024)

Unveiling the impact of textile materials to prevent viral infections: Urgency for awareness and public safety† - Muhammad Zaryab Waleed; Khezina Rafiq; Muhammad Zeeshan Abid; Muhammad Burhan; Raed H. Althomali; Shahid Iqbal; Ejaz Hussain (Journal of Environmental Chemical Engineering, 2024)

Selection of ionic liquid electrolytes for high-performing lithium-sulfur batteries: An experiment-guided high-throughput machine learning analysis - Aysegul Kilic; Omar Abdelaty; Muhammad Zeeshan; Alper Uzun; Ramazan Yildirim; Damla Eroglu (Chemical Engineering Journal, 2024)

Construction and Utilization of Innovative Zeolite/Perovskite/Graphene Oxide, Zeolite/Chitosan/Graphene Oxide, and Zeolite/Biochar/Graphene Oxide Nanohybrid Composites for Adsorptive Remediation of Cationic Dye from Wastewater - Nageen Mushtaq; Ruba Munir; Muhammad Zia-ur-Rehman; Zia ul-Haq; Muhammad Zeeshan Bashir; Amna Muneer; Hina Ambreen; Saima Noreen (Water Conservation Science and Engineering, 2024)

Transcutaneous Delivery of Dexamethasone Sodium Phosphate Via Microneedle-Assisted Iontophoretic Enhancement – A Potential Therapeutic Option for Inflammatory Disorders - Muhammad Sohail Arshad; Saad Hussain; Saman Zafar; Sadia Jafar Rana; Tahir Ali Chohan; Muhammad Hamza; Kazem Nazari; Zeeshan Ahmad (Pharmaceutical Research, 2024)

Bioactive compounds isolated from Solanum nigrum remarkably inhibit cancerous activity in cancer cell lines - Aisha Nawaz; Adil Jamal; Amina Arif; Shumaila Kiran; Muhammad Naveed Shahid; Shafia Arshad; Zeeshan Shamim (South African Journal of Botany, 2024)

Influences of emerging drying technologies on rice quality - Naveed Mahmood; Yanhong Liu; Xu Zheng; Zeeshan Munir; R. Pandiselvam; Yue Zhang; Mansab Ali Saleemi; Harimana Yves; Muhammad Sufyan; Dengwen Lei (Food Research International, 2024)

Comparative study of light-emitting cement and polymer mortars for sustainable building applications: performance evaluation and analysis - Muhammad Ali Sikandar; Zeeshan Khan; Muhammad Haris Javed; Muhammad Tariq Bashir; Easa Khan; Md. Munir Hayet Khan; Azhar Qazi (Innovative Infrastructure Solutions, 2024)

Spatiotemporal investigation of near-surface CH4 and factors influencing CH4 over South, East, and Southeast Asia - Muhammad Athar Khaliq; Farhan Mustafa; Shafeeq Ur Rehman; Muhammad Shahzaman; Zeeshan Javed; Muhammad Sagir; Safdar Bashir; Hongchao Zuo (Science of The Total Environment, 2024)

RETRACTED: Mycorrhizosphere bacteria inhibit greenhouse gas emissions from microplastics contaminated soil by regulating soil enzyme activities and microbial community structure - Zeeshan Khan; Tariq Shah; Ghulam Haider; Fazal Adnan; Zeshan Sheikh; Mohamed A. El-Sheikh; Muhammad Faraz Bhatti; Parvaiz Ahmad (Journal of Environmental Management, 2024)

Genome-wide identification and in-silico expression analysis of CCO gene family in sunflower (Helianthus annuus) against abiotic stress - Adnan Sami; Muhammad Zeeshan Haider; Muhammad Shafiq; Saleh Sadiq; Farooq Ahmad (Plant Molecular Biology, 2024)
Carotenoid cleavage oxygenases (CCOs) enzymes play an important role in plant growth and development by producing a wide array of apocarotenoids and their derivatives. These compounds are vital for colouring flowers and fruits and synthesizing plant hormones such as abscisic acid and strigolactones. Despite their importance, the gene family responsible for CCO enzymes in sunflowers has not been identified. In this study, we identify the CCO genes of the sunflower plant to fill this knowledge gap. Phylogenetic and synteny analysis indicated that the Helianthus annuus CCO (HaCCO) genes were conserved in different plant species and they could be divided into three subgroups based on their conserved domains. Analysis using MEME tool and multiple sequence alignment identified conserved motifs in the HaCCO gene sequence. Cis -regulatory elements (CREs) analysis of the HaCCO genes indicated the presence of various responsive elements related to plant hormones, development, and responses to both biotic and abiotic stresses. This implies that these genes may respond to plant hormones, developmental cues, and drought stress, offering potential applications in the development of more resistant crops. Genes belonging to the 9-cis-epoxy carotenoid dioxygenases (NCED) subgroups predominantly exhibited chloroplast localization, whereas the genes found in other groups are primarily localized in the cytoplasm. These 21 identified HaCCOs were regulated by 60 miRNAs, indicating the crucial role of microRNAs in gene regulation in sunflowers. Gene expression analysis under drought stress revealed significant up-regulation of HaNCED16 and HaNCED19 , genes that are pivotal in ABA hormone biosynthesis. During organ-specific gene expression analysis, HaCCD12 and HaCCD20 genes exhibit higher activity in leaves, indicating a potential role in leaf pigmentation. This study provides a foundation for future research on the regulation and functions of the CCO gene family in sunflower and beyond. There is potential for developing molecular markers that could be employed in breeding programs to create new sunflower lines resistant to biotic and abiotic stresses.

Depositional and Bio-Sequence Stratigraphic Framework of Late Cretaceous Kawagarh Formation, Kala-Chitta Range, Pakistan: Equivalent of Gurpi Formation (Iran) - Muhammad Awais; Bilal Wadood; Muhammad Ishaq; Muhammad Bilal; Zeeshan Zafar; Nasar Khan; Aminullah Khan (Journal of Earth Science, 2024)

Predicting asphaltene adsorption on Fe3O4 nanoparticle using machine learning algorithms - Syed Imran Ali; Shaine Mohammadali Lalji; Usama Ahsan; Syed Muhammad Ali; Yassar Kamal Zia; Sajid Hussain; Muneeb Burney; Muhammad Qasim; Zeeshan Ahmad Arfeen (Arabian Journal of Geosciences, 2024)

Unveiling Intricacies of Mango Malformation Dynamics Caused by Fusarium solani Through Extensive Field Surveys and Laboratory, Epidemiology, and Model-Based Insights - Abdurrehman; Talha Mansoor; Muhammad Nasir Subhani; Muhammad Tariq Malik; Ammarah Hasnain; Aqleem Abbas; Abdulwahed Fahad Alrefaei; Haider Ali; Muhammad Zeeshan Hassan; Syed Atif Hasan Naqvi (Applied Fruit Science, 2024)

Correction to: Mycorrhizosphere bacteria inhibit chromium uptake and phytotoxicity by regulating proline metabolism, antioxidant defense system, and aquaporin gene expression in tomato - Tariq Shah; Zeeshan Khan; Tahani Awad Alahmadi; Ayesha Imran; Muhammad Asad; Shah Rukh Khan; Mohammad Javed Ansari (Environmental Science and Pollution Research, 2024)

Mycorrhizosphere bacteria inhibit chromium uptake and phytotoxicity by regulating proline metabolism, antioxidant defense system, and aquaporin gene expression in tomato - Tariq Shah; Zeeshan Khan; Tahani Awad Alahmadi; Ayesha Imran; Muhammad Asad; Shah Rukh Khan; Mohammad Javed Ansari (Environmental Science and Pollution Research, 2024)

Energy potential assessment and geospatial site suitability analysis for crop residue-based power plants in Pakistan - Salsabeel Fatima; Muhammad Zeeshan (Sustainable Production and Consumption, 2024)

Temporal profiling of physiological, histological, and transcriptomic dissection during auxin-induced adventitious root formation in tetraploid Robinia pseudoacacia micro-cuttings - Saleem Uddin; Muhammad Zeeshan Munir; Eduardo Larriba; José Manuel Pérez-Pérez; Sadia Gull; Tariq Pervaiz; Umer Mahmood; Zahid Mahmood; Yuhan Sun; Yun Li (Planta, 2024)

RETRACTED: Straw incorporation into microplastic-contaminated soil can reduce greenhouse gas emissions by enhancing soil enzyme activities and microbial community structure - Tariq Shah; Zeeshan Khan; Muhammad Asad; Ayesha Imran; Muhammad Bilal Khan Niazi; Raf Dewil; Ajaz Ahmad; Parvaiz Ahmad (Journal of Environmental Management, 2024)

Synthetic bacterial community derived from Astragalus mongholicus and plant-plant interactions inhibit cadmium uptake by modulating gene expression, antioxidant system and carbohydrate metabolism under cadmium contaminated soil - Tariq Shah; Zeeshan Khan; Muhammad Asad; Roberto D’amato; Abdulaziz Abdullah Alsahli; Parvaiz Ahmad (Journal of Environmental Chemical Engineering, 2024)

Emerging developments in polymeric nanocomposite membrane-based filtration for water purification: A concise overview of toxic metal removal - Arfa Iqbal; Emre Cevik; Ayyaz Mustafa; Talal F. Qahtan; Muhammad Zeeshan; Ayhan Bozkurt (Chemical Engineering Journal, 2024)

Foliar Glutamine Application Improves Grain Yield and Nutritional Quality of Field-Grown Maize (Zea mays L.) Hybrid ZD958 - Md Monirul Islam; Mahmood Ul Hassan; Muhammad Ishfaq; Farhana Alam Ripa; Faisal Nadeem; Zeeshan Ahmad; Jiuliang Xu; Peng Ning; Xuexian Li (Journal of Plant Growth Regulation, 2024)

Determination of Salinity Tolerance in Pigmented Rice Genotypes at Seedling Stage - Zeeshan Ali; Muhammad Naeem; Hafiz Ghulam Muhu-Din Ahmed (Journal of Crop Health, 2024)

RETRACTED: Synergistic effect of silicon and arbuscular mycorrhizal fungi reduces cadmium accumulation by regulating hormonal transduction and lignin accumulation in maize - Shah Rukh Khan; Zubair Ahmad; Zeeshan Khan; Umair Khan; Muhammad Asad; Tariq Shah (Chemosphere, 2024)

Effective biological control of Lentil (Lens culinaris) Fusarium wilt and plant growth promotion through native Rhizobacteria - Javeria Ayub; Ayesha Tahir; Umer Iqbal; Huma Ayub; Muhammad Zeeshan Hyder; Amna Kiyani; Fauzia Yusuf Hafeez; Muhammad Kashif Ilyas; Abdul Ghafoor; Tayyaba Yasmin (Physiological and Molecular Plant Pathology, 2024)

Advances/Scope and prospects of g-C3N4 derived fascinating photocatalyst as a leading route towards solar energy adaption - Asif Hayat; Muhammad Sohail; Zeeshan Ajmal; Hala H. Abd El-Gawad; Djamel Ghernaout; Yas Al-Hadeethi; Saleem Raza; Yasin Orooji (Journal of Cleaner Production, 2024)

RETRACTED: Alleviation of microplastic toxicity in soybean by arbuscular mycorrhizal fungi: Regulating glyoxalase system and root nodule organic acid - Zeeshan Khan; Tariq Shah; Muhammad Asad; Khadija Amjad; Abdulaziz Abdullah Alsahli; Parvaiz Ahmad (Journal of Environmental Management, 2024)

Seasonal variations in dissolved organic matter concentration and composition in an outdoor system for bank filtration simulation - Muhammad Zeeshan; Omamah Ali; Shamas Tabraiz; Aki Sebastian Ruhl (Journal of Environmental Sciences, 2024)

Magnetic solid phase extraction of aminoglycosides residue in chicken egg samples using Fe3O4-GO-Agarose-Chitosan composite - Muhammad Sajjad; Rasmiah Almufarij; Zeeshan Ali; Muhammad Sajid; Nadeem Raza; Suryyia Manzoor; Muhammad Hayat; Ehab A. Abdelrahman (Food Chemistry, 2024)

Retraction Note: A new cationic palladium(II) dithiocarbamate exhibits anti-inflammatory, analgesic, and antipyretic activities through inhibition of inflammatory mediators in in vivo models - Muhammad Naveed; Shahan Zeb Khan; Sara Zeeshan; Adnan Khan; Bushra Shal; Ayesha Atiq; Hussain Ali; Rahim Ullah; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Predicting wettability of mineral/CO2/brine systems via data-driven machine learning modeling: Implications for carbon geo-sequestration - Zeeshan Tariq; Muhammad Ali; Aliakbar Hassanpouryouzband; Bicheng Yan; Shuyu Sun; Hussein Hoteit (Chemosphere, 2023)

Performance comparison of a photosynthetic and mechanically aerated microbial fuel cell for wastewater treatment and bioenergy generation using different anolytes - Zia Ullah; Zeshan Sheikh; Waqas Qamar Zaman; Muhammad Zeeshan; Waheed Miran; Jiansheng Li; Muhammad Abdul Nasir Khan; Sahar Saleem; Shanza Shabbir (Journal of Water Process Engineering, 2023)

Surface sensitization of TiO2 via Pd/Rb2O cocatalysts: Mechanistic insights to the arsenic elimination from ground drinking water† - Kashaf Ul Sahar; Khezina Rafiq; Muhammad Zeeshan Abid; Ubaid ur Rehman; Ujala Quyyum; Abdul Rauf; Ejaz Hussain (Journal of Environmental Chemical Engineering, 2023)

Enhancing wettability prediction in the presence of organics for hydrogen geo-storage through data-driven machine learning modeling of rock/H2/brine systems - Zeeshan Tariq; Muhammad Ali; Nurudeen Yekeen; Auby Baban; Bicheng Yan; Shuyu Sun; Hussein Hoteit (Fuel, 2023)

Growth of tunable Au-BaO@TiO2/CdS heterostructures: Acceleration of hydrogen evolution from water splitting - Mamoona Sabir; Khezina Rafiq; Muhammad Zeeshan Abid; Ujala Quyyum; Syed Shoaib Ahmad Shah; Muhammad Faizan; Abdul Rauf; Shahid Iqbal; Ejaz Hussain (Fuel, 2023)

Synergized toxicity exhibited by indigenous entomopathogenic fungal strains, plant extracts and synthetic insecticides against fall armyworm Spodoptera frugiperda (J.E. Smith) under laboratory and semi-field conditions - Kanwer Shahzad Ahmed; Muhammad Zeeshan Majeed; Samy Sayed; Bader Z. Albogami; Laila A. Al-Shuraym; Hina Safdar; Ikram Ul Haq; Abu Bakar Muhammad Raza (Journal of Plant Diseases and Protection, 2023)

Fabrication and Evaluation of Differential Release Bilayer Tablets of Clarithromycin and Levofloxacin by 3D Printing - Qazi Amir Ijaz; Sumera Latif; Sumaira Irum Khan; Memoona Rashid; Hafsa Afzal; Nasrullah Jan; Zeeshan Javaid; Muhammad Sarfraz; Amjad Hussain; Muhammad Sohail Arshad; Nadeem Irfan Bukhari; Nasir Abbas (Journal of Pharmaceutical Innovation, 2023)

Comparative Analysis of IgG Antibody Titers Induced by Three Different SARS-COV-2 Vaccines in Healthy Adults of Pakistan - Nayab Batool Rizvi; Hassam Farooq; Qaiser Alam Khan; Muhammad Zeeshan Rana; Sehrish Zaffar; Muhammad Shahid; Nazim Hussain (Current Microbiology, 2023)

Silicon inhibits cadmium uptake by regulating the genes associated with the lignin biosynthetic pathway and plant hormone signal transduction in maize plants - Tariq Shah; Zeeshan Khan; Shah Rukh Khan; Ayesha Imran; Muhammad Asad; Ajaz Ahmad; Parvaiz Ahmad (Environmental Science and Pollution Research, 2023)

Policies and regulations for solar photovoltaic end-of-life waste management: Insights from China and the USA - Amjad Ali; Sheraz Alam Malik; Md Shafiullah; Muhammad Zeeshan Malik; Md Hasan Zahir (Chemosphere, 2023)

Genomic and biotechnological potential of a novel oil-degrading strain Enterobacter kobei DH7 isolated from petroleum-contaminated soil - Muhammad Zohaib Nawaz; Chunyan Xu; Majjid A. Qaria; Syed Zeeshan Haider; Hafiz Rameez Khalid; Huda Ahmed Alghamdi; Iqrar Ahmad Khan; Daochen Zhu (Chemosphere, 2023)

A walnut shell biochar-nano zero-valent iron composite membrane for the degradation of carbamazepine via persulfate activation - Yongtao Xue; Mohammadreza Kamali; Alina Liyakat; Maud Bruggeman; Zeeshan Muhammad; Barbara Rossi; Maria Elisabete V. Costa; Lise Appels; Raf Dewil (Science of The Total Environment, 2023)

Fates of potentially persistent and mobile organic substances in embedded outdoor columns for artificial groundwater recharge simulation - Muhammad Zeeshan; Aki Sebastian Ruhl (Water Research, 2023)

Molecular characterization of azoreductase and its potential for the decolorization of Remazol Red R and Acid Blue 29 - Ghulam Mustafa; Muhammad Tariq Zahid; Mayur Bharat Kurade; Swapnil Mahadeo Patil; Farah Rauf Shakoori; Zeeshan Shafiq; Sidra Ihsan; Yongtae Ahn; Azmat Ali Khan; Amel Gacem; Byong-hun Jeon (Environmental Pollution, 2023)

Impact of graded levels of coated calcium butyrate on growth performance and serological indices during pre-weaning stage in Holstein calves - Abdur Rahman; Muhammad Furhan Arshad; Shah Nawaz; Zafar Hayat; Syed Ehtisham ul Haque; Saima Saima; Akhtar Rasool Asif; Muawuz Ijaz; Muhammad Zeeshan Anwar (Tropical Animal Health and Production, 2023)

Seismic Interactions Between Northern Terminus of Ornahc-Nal and Hoshab Faults Based on Source Mechanism Investigation of 06 May 2022 Mw 5.4 Khuzdar Earthquake - Ahmed Zeeshan Shaukat; Mohammad Tahir; Tahir Iqbal; Talat Iqbal; Muhammad Ali Shah (Pure and Applied Geophysics, 2023)

RETRACTED: Strigolactone decreases cadmium concentrations by regulating cadmium localization and glyoxalase defense system: Effects on nodules organic acids and soybean yield - Tariq Shah; Muhammad Asad; Zeeshan Khan; Khadija Amjad; Abdulaziz Abdullah Alsahli; Roberto D'amato (Chemosphere, 2023)

Fates of selected pharmaceuticals in a large recirculated mesocosm with a pond and bank filtration - Muhammad Zeeshan; Silke Pabst; Eduard Sandyk; Aki Sebastian Ruhl (Science of The Total Environment, 2023)

A comparative techno-economic analysis of combined oil and power production from pyrolysis and co-pyrolysis plants utilizing rice straw and scrap rubber tires - Shoaib Raza Khan; Muhammad Zeeshan; Salsabeel Fatima; Daniel Ciolkosz; Ioanna Dimitriou; Hongyue Jin (Fuel, 2023)

Melatonin Mitigates Salt-Induced Growth Inhibition Through the Regulation of Carbohydrate and Nitrogen Metabolism in Tomato Seedlings - Mohammad Shah Jahan; Guihua Li; Dasen Xie; Reham Farag; Md. Mahadi Hasan; Nadiyah M. Alabdallah; Nadi Awad Al-Harbi; Salem Mesfir Al-Qahtani; Muhammad Zeeshan; Jamal Nasar; Muhammad Ahsan Altaf; Md Atikur Rahman (Journal of Soil Science and Plant Nutrition, 2023)

Improved Transdermal Delivery of Rabies Vaccine using Iontophoresis Coupled Microneedle Approach - Muhammad Sohail Arshad; Saad Hussain; Saman Zafar; Sadia Jafar Rana; Nadia Ahmad; Najmusama Abdul Jalil; Zeeshan Ahmad (Pharmaceutical Research, 2023)

Clinicopathological profile of peritoneal tuberculosis and a new scoring model for predicting mortality: an international ID-IRI study - Alpaslan Tanoglu; Hakan Erdem; Jon S. Friedland; Handan Ankaralı; Jose Fernando Garcia-Goez; Ayse Albayrak; Amani El-Kholy; Sevil Alkan Ceviker; Fatma Amer; Serpil Erol; Ilad Alavi Darazam; Mohammad Mahdi Rabiei; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

A modified experimental approach to determine formation porosity from rock cuttings - Semab Tariq; Zeeshan Khan; Allah Bakhsh; Syed Jamal ud Din; Azizullah Shaikh; Habib Ur Rehman; Rashid Sher Muhammad; Liang Zhang (Arabian Journal of Geosciences, 2023)

Variations in cold flow and physical properties of Northern Pakistan gas condensate oil after interacting with different polymeric drilling mud systems - Shaine Mohammadali Lalji; Syed Imran Ali; Sajid Hussain; Syed Muhammad Ali; Zeeshan Ali Lashari (Arabian Journal of Geosciences, 2023)

Economic and non-economic drivers of tourism: bidirectional causality of tourism and environment for South Asian economies - Salman Wahab; Bilal Ahmed; Muhammad Imran; Adnan Safi; Zeeshan Wahab (Environmental Science and Pollution Research, 2023)

Synthesis and two-step KOH based activation of porous biochar of wheat straw and waste tire for adsorptive exclusion of chromium (VI) from aqueous solution; thermodynamic and regeneration study - Usama Jamil; Muhammad Zeeshan; Shoaib Raza Khan; Sara Saeed (Journal of Water Process Engineering, 2023)

The influence of civilized city honorary title on the urban innovation capacity - Jiabin han; Ziyi Chen; Muhammad Zeeshan; Alam Rehman; Irfan Ullah; Suleman Sarwar (Environment, Development and Sustainability, 2023)

The fate of nitrification and urease inhibitors in simulated bank filtration - Muhammad Zeeshan; Marco Scheurer; Christina Förster; Christine Kuebeck; Aki Sebastian Ruhl; Sondra Klitzke (Journal of Environmental Management, 2023)

Effects of Biotic and Abiotic Aging Techniques on Physiochemical and Molecular Characteristics of Biochar and Their Impacts on Environment and Agriculture: A Review - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman; Yanyan Li; Akash Tariq; Muhammad Rizwan (Journal of Soil Science and Plant Nutrition, 2023)

Emissions and efficiency of an improved conventional liquefied petroleum gas cookstoves in Pakistan - Muhammad Usman; Muhammad Ammar; Muddassir Ali; Muhammad Zafar; Muhammad Zeeshan (Environment, Development and Sustainability, 2023)

Characteristics and prediction of paleo-environment of Eocene Jatta Gypsum, Kohat Basin, Pakistan - Hassanat Ullah; Zhong Jianhua; Muhammad Kashif; Shahab Aman e Room; Zeeshan Zafar; Saif Ur Rehman (Arabian Journal of Geosciences, 2023)

Green metal oxides coated biochar nanocomposites preparation and its utilization in vertical flow constructed wetlands for reactive dye removal: Performance and kinetics studies - Ruba Munir; Khuram Ali; Syed Abbas Zilqurnain Naqvi; Amna Muneer; Muhammad Zeeshan Bashir; Muhammad Aamer Maqsood; Saima Noreen (Journal of Contaminant Hydrology, 2023)

The promoters of OsGLP genes exhibited differentially methylated sites under drought and salt stress in rice cultivars - Jazba Anum; Charlotte O’Shea; Karen Skriver; Muhammad Saeed; Muhammad Zeeshan Hyder; Sumaira Farrakh; Tayyaba Yasmin (Euphytica, 2023)

Isolation, characterization and larvicidal potential of indigenous soil inhabiting bacteria against larvae of southern house mosquito (Culex quinquefasciatus Say) - Sohaib Iftikhar; Muhammad Asam Riaz; Muhammad Zeeshan Majeed; Muhammad Afzal; Anam Ali; Mubshara Saadia; Zulfiqar Ali; Sohail Ahmed (International Journal of Tropical Insect Science, 2023)

Supplier transaction, TMT characteristics, and the persistence of earnings: do their relationship contribute towards sustainable performance of Chinese listed manufacturing sector firms? - Wang Minghua; Yang Tao; Muhammad Zeeshan; Alam Rehman (Environmental Science and Pollution Research, 2023)

Asymmetric nexus between Bitcoin, gold resources and stock market returns: Novel findings from quantile estimates - Zhenzhen Jia; Sunil Tiwari; Jianhua Zhou; Muhammad Umar Farooq; Zeeshan Fareed (Resources Policy, 2023)

Antioxidant enzymes activity and gene expression in wheat-stripe rust interaction at seedling stage - Zainy Zainy; Muhammad Fayyaz; Tayyaba Yasmin; Muhammad Zeeshan Hyder; Waseem Haider; Sumaira Farrakh (Physiological and Molecular Plant Pathology, 2023)

Synthesis of Metal Hydroxyapatite Nanoparticles and Their Application, Behavior, and Mechanism in the Removal of Cationic Dye Red 3R from Aqueous Media - Ujala Shafqaat; Ruba Munir; Khuram Ali; Muhammad Ahsan; Muhammad Zeeshan Bashir; Saima Noreen (Water, Air, & Soil Pollution, 2023)

Engineering of tetanus toxoid-loaded polymeric microneedle patches - Muhammad Sohail Arshad; Shafaq Gulfam; Saman Zafar; Najmusama Abdul Jalil; Nadia Ahmad; Omar Qutachi; Ming-Wei Chang; Neenu Singh; Zeeshan Ahmad (Drug Delivery and Translational Research, 2023)

Cellulose/inorganic nanoparticles-based nano-biocomposite for abatement of water and wastewater pollutants - Zhen Zhang; Abdulrazaq Ibrahim Said Ahmed; Muhammad Zeeshan Malik; Nisar Ali; Adnan khan; Farman Ali; Mohamed Osman Hassan; Badr A. Mohamed; Jakub Zdarta; Muhammad Bilal (Chemosphere, 2023)

Multi-objective optimization of concentrated solar power plants from an energy-water-environment nexus perspective under distinct climatic conditions – Part B: Environ-economic analysis - Momina Ahmad; Muhammad Zeeshan (Journal of Cleaner Production, 2023)

Physiological and transcriptomic study reveal SeNPs-mediated AsIII stress detoxification mechanisms involved modulation of antioxidants, metal transporters, and transcription factors in Glycine max L. (Merr.) roots - Muhammad Zeeshan; Yu Xin Hu; Xiao Hong Guo; Chen Yu Sun; Abdul Salam; Shakeel Ahmad; Ihsan Muhammad; Jamal Nasar; Mohammad Shah Jahan; Shah Fahad; Xun Bo Zhou (Environmental Pollution, 2023)

Polyelectrolyte multilayers coating of aliphatic polyamide anion-exchange membranes to increase monovalent/divalent anions selectivity in electrodialysis - Muhammad Ahmad; Mahmood Ahmed; Shabbir Hussain; Abid Ali; Manzar Zahra; Muhammad Imran Din; Zeeshan Mustafa (Desalination, 2023)

Observed and predicted precipitation variability across Pakistan with special focus on winter and pre-monsoon precipitation - Fasiha Safdar; Muhammad Fahim Khokhar; Fatimah Mahmood; Muhammad Zeeshan Ali Khan; Muhammad Arshad (Environmental Science and Pollution Research, 2023)

Low Irrigation Water Improves Biomass Saccharification, Photosynthetic Pigments of Maize, and Minimizes Nitrate Nitrogen Leaching - Ihsan Muhammad; Li Yang; Shakeel Ahmad; Saqib Farooq; Ahmad Khan; Muhammad Zeeshan; Xun Bo Zhou (Journal of Soil Science and Plant Nutrition, 2022)

The molecular genetics of human appendicular skeleton - Safeer Ahmad; Muhammad Zeeshan Ali; Muhammad Muzammal; Fayaz Ahmad Mir; Muzammil Ahmad Khan (Molecular Genetics and Genomics, 2022)

Role of financial stability, technological innovation, and renewable energy in achieving sustainable development goals in BRICS countries - Salman Wahab; Muhammad Imran; Adnan Safi; Zeeshan Wahab; Dervis Kirikkaleli (Environmental Science and Pollution Research, 2022)

Omics: a tool for resilient rice genetic improvement strategies - Muhammad Naeem; Zeeshan Ali; Anzal Khan; Sami-Ul-Allah; Hassan Javed Chaudhary; Javeria Ashraf; Faheem Shahzad Baloch (Molecular Biology Reports, 2022)

A review of the global climate change impacts, adaptation, and sustainable mitigation measures - Kashif Abbass; Muhammad Zeeshan Qasim; Huaming Song; Muntasir Murshed; Haider Mahmood; Ijaz Younis (Environmental Science and Pollution Research, 2022)

Phycoremediation of textile effluents with enhanced efficacy of biodiesel production by algae and potential use of remediated effluent for improving growth of wheat - Muhammad Rashid Waqas; Sajid Mahmood Nadeem; Muhammad Yahya Khan; Zeeshan Ahmad; Liaqat Ali; Hafiz Naeem Asghar; Azeem Khalid (Environmental Science and Pollution Research, 2022)

Clean and sustainable transportation through electric vehicles — a user survey of three-wheeler vehicles in Pakistan - Mohammad Aamir Khan; Syed Fawad Bokhari; Aazir Khan; Muhammad Saad Amjad; Arooj Mobasher Butt; Muhammad Zeeshan Rafique (Environmental Science and Pollution Research, 2022)

Trade openness and urbanization impact on renewable and non-renewable energy consumption in China - Jiabin han; Muhammad Zeeshan; Irfan Ullah; Alam Rehman; Fakhr E Alam Afridi (Environmental Science and Pollution Research, 2022)

In vitro synergy of entomopathogenic fungi and differential-chemistry insecticides against armyworm Spodoptera litura Fabricius (Lepidoptera: Noctuidae) - Zainab Batool; Muhammad Asam Riaz; Samy Sayed; Muhammad Zeeshan Majeed; Sohail Ahmed; Sami Ullah (International Journal of Tropical Insect Science, 2022)

Systematic analysis of HD-ZIP transcription factors in sesame genome and gene expression profiling of SiHD-ZIP class I entailing drought stress responses at early seedling stage - Maryam Mehmood; Muhammad Jadoon Khan; Muhammad Jawad Khan; Nadeem Akhtar; Fizza Mughal; Syed Tahir Abbas Shah; Muhammad Zeeshan Hyder; Sumaira Farrakh; Irfan Sadiq (Molecular Biology Reports, 2022)

Re-evaluating the dynamic role of shadow economy and environmental policy stringency in the energy-growth nexus in China - Lu Lu; Xiaolei Fan; Sana Ullah; Muhammad Zeeshan Younas (Environmental Science and Pollution Research, 2022)

Correction to: Biochemical characterization of Aedes aegypti (Linnaeus) (Diptera: Culicidae) resistance to deltamethrin, fipronil, and imidacloprid - Muhammad Waqas Sumra; Shoaib Freed; Muhammad Sheraz Shah; Muhammad Zeeshan Nazar; Sikandar Hussain; Afifa Naeem (Environmental Monitoring and Assessment, 2022)

RNA interference-mediated knockdown of odorant-binding protein 2 and MP58 gene causes mortality in Myzus persicae - Iqra Mahmood; Amber Afroz; Muhammad Faheem Malik; Nadia Zeeshan; Muhammad Ramzan Khan; Umer Rashid; Muhammad Azmat Ullah Khan; Naeem Mehmood Ashraf; Sadia Alam (International Journal of Tropical Insect Science, 2022)

Agricultural system modeling: current achievements, innovations, and future roadmap - Zeeshan Ahmed; Dongwei Gui; Zhiming Qi; Yi Liu; Yunfei Liu; Muhammad Azmat (Arabian Journal of Geosciences, 2022)

Feedstock type, pyrolysis temperature and acid modification effects on physiochemical attributes of biochar and soil quality - Ghulam Murtaza; Zeeshan Ahmed; Muhammad Usman (Arabian Journal of Geosciences, 2022)

Intron-containing hairpin RNA interference vector for OBP8 show promising mortality in peach potato aphid - Amber Afroz; Safeena Aslam; Umer Rashid; Muhammad Faheem Malik; Nadia Zeeshan; Muhammad Ramzan Khan; Muhammad Qasim Shahzad But; Sabaz Ali Khan (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

A novel protein truncating mutation in L2HGDH causes L-2-hydroxyglutaric aciduria in a consanguineous Pakistani family - Muhammad Muzammal; Muhammad Zeeshan Ali; Beatrice Brugger; Jasmin Blatterer; Safeer Ahmad; Sundas Taj; Syed Khizar Shah; Saadullah Khan; Christian Enzinger; Erwin Petek; Klaus Wagner; Muzammil Ahmad Khan; et al. (Metabolic Brain Disease, 2022)
Background L-2-hydroxyglutaric aciduria (L2HGA) is a rare neurometabolic disorder that occurs due to accumulation of L-2-hydroxyglutaric acid in the cerebrospinal fluid (CSF), plasma and urine. The clinical manifestation of L2HGA includes intellectual disability, cerebellar ataxia, epilepsy, speech problems and macrocephaly. Methods In the present study, we ascertained a multigenerational consanguineous Pakistani family with 5 affected individuals. Clinical studies were performed through biochemical tests and brain CT scan. Locus mapping was carried out through genome-wide SNP genotyping, whole exome sequencing and Sanger sequencing. For in silico studies protein structural modeling and docking was done using I-TASSER, Cluspro and AutoDock VINA tools. Results Affected individuals presented with cognitive impairment, gait disturbance, speech difficulties and psychomotor delay. Radiologic analysis of a male patient revealed leukoaraiosis with hypoattenuation of cerebral white matter, suggestive of hypomyelination. Homozygosity mapping in this family revealed a linkage region on chromosome 14 between markers rs2039791 and rs781354. Subsequent whole exome analysis identified a novel frameshift mutation NM_024884.3:c.180delG, p.(Ala62Profs*24) in the second exon of L2HGDH . Sanger sequencing confirmed segregation of this mutation with the disease phenotype. The identification of the most N-terminal loss of function mutation published thus far further expands the mutational spectrum of L2HGDH.

Impact of the mixture verses solo residue management and climatic conditions on soil microbial biomass carbon to nitrogen ratio: a systematic review - Ihsan Muhammad; Jun Wang; Ahmad Khan; Shakeel Ahmad; Li Yang; Izhar Ali; Muhammad Zeeshan; Saif Ullah; Shah Fahad; Shamsher Ali; Xun Bo Zhou (Environmental Science and Pollution Research, 2021)

Morpho-physiological investigations in transgenic tomato (Solanum lycopersicum L.) over expressing OsRGLP1 gene - Sumera Perveen; Tehmina Ahsan Khan; Humaira Shaheen; Rabia Naz; Muhammad Zeeshan Hyder; Bushra Ijaz; S. M. Saqlan Naqvi; Tayyaba Yasmin (In Vitro Cellular & Developmental Biology - Plant, 2021)

Assessment of Microscopic Detection of Malaria with Nested Polymerase Chain Reaction in War-Torn Federally Administered Tribal Areas of Pakistan - Muhammad Faisal Nadeem; Aamer Ali Khattak; Nadia Zeeshan; Usman Ayub Awan; Adnan Yaqoob (Acta Parasitologica, 2021)

Mapping flood extend and its impact on land use/land cover and settlements variations: a case study of Layyah District, Punjab, Pakistan - Shan-e-hyder Soomro; Caihong Hu; Muhammad Waseem Boota; Mairaj Hyder Alias Aamir Soomro; Shengqi Jian; Zeeshan Zafar; Xiaoping Li (Acta Geophysica, 2021)

Essential oil composition and antibacterial activity of Canarium strictum Roxb. resin - Halima Tahir; Nadeem Muhammad; Azeem Intisar; Muhammad Imran Din; Uzma Qaisar; Muhammad Abdul Qadir; Noor Ul Ain; Zeeshan Ahmad; Pakeeza Aziz; Muhammad Khurram Shahzad; Irshad Hussain (Plant Biosystems, 2021)

Correction to: Exploring determinants of financial system and environmental quality in high-income developed countries of the world: the demonstration of robust penal data estimation techniques - Muhammad Zeeshan; Jiabin Han; Alam Rehman; Irfan Ullah; Fakhr E Alam Afridi (Environmental Science and Pollution Research, 2021)

Exploring determinants of financial system and environmental quality in high-income developed countries of the world: the demonstration of robust penal data estimation techniques - Muhammad Zeeshan; Jiabin Han; Alam Rehman; Irfan Ullah; Fakhr E Alam Afridi (Environmental Science and Pollution Research, 2021)

Role of nanotechnology in animal production and veterinary medicine - Ahmad Ali; Muhammad Ijaz; Yasir Razzaq Khan; Hina Afzal Sajid; Kashif Hussain; Ameer Hamza Rabbani; Muhammad Shahid; Omer Naseer; Awais Ghaffar; Muhammad Anas Naeem; Muhammad Zeeshan Zafar; Amir Iftikhar Malik; et al. (Tropical Animal Health and Production, 2021)

Venlafaxine demonstrated anti-arthritic activity possibly through down regulation of TNF-α, IL-6, IL-1β, and COX-2 - Mater Hussen Mahnashi; Zeeshan Jabbar; Alamgeer; Hafiz Muhammad Irfan; Mulazim Hussain Asim; Muhammad Akram; Ahmed Saif; Mohammed Abdulrahman Alshahrani; Mohammed Ali Alshehri; Saeed Ahmed Asiri (Inflammopharmacology, 2021)

Environmental impact and diversity of protease-producing bacteria in areas of leather tannery effluents of Sialkot, Pakistan - Muhammad Qasim Butt; Nadia Zeeshan; Naeem Mahmood Ashraf; Muhammad Aftab Akhtar; Hina Ashraf; Amber Afroz; Aqsa Shaheen; Shumaila Naz (Environmental Science and Pollution Research, 2021)

Urban noise assessment and its nonauditory health effects on the residents of Chiniot and Jhang, Punjab, Pakistan - Zia Ur Rahman Farooqi; Iftikhar Ahmad; Nukshab Zeeshan; Predrag Ilić; Muhammad Imran; Muhammad Farhan Saeed (Environmental Science and Pollution Research, 2021)

Biochemical characterization of Aedes aegypti (Linnaeus) (Diptera: Culicidae) resistance to deltamethrin, fipronil, and imidacloprid - Muhammad Waqas Sumra; Shoaib Freed; Muhammad Sheraz Shah; Muhammad Zeeshan Nazar; Sikandar Hussain; Afifa Naeem (Environmental Monitoring and Assessment, 2021)

Comparative Effect of Fertilization Practices on Soil Microbial Diversity and Activity: An Overview - Muhammad Shehryar Sabir; Farah Shahzadi; Farooq Ali; Qismat Shakeela; Zeeshan Niaz; Shehzad Ahmed (Current Microbiology, 2021)

Isopentenyl Diphosphate Isomerase (IPI) Gene Silencing Negatively Affects Patchouli Alcohol Biosynthesis in Pogostemon cablin - Wuping Yan; Yuzhang Yang; Yougen Wu; Jing Yu; Junfeng Zhang; Dongmei Yang; Zeeshan Ul Haq Muhammad (Plant Molecular Biology Reporter, 2021)

Biochar for the Management of Nutrient Impoverished and Metal Contaminated Soils: Preparation, Applications, and Prospects - Ghulam Murtaza; Allah Ditta; Naseer Ullah; Muhammad Usman; Zeeshan Ahmed (Journal of Soil Science and Plant Nutrition, 2021)

Paclobutrazol Improves Sesame Yield by Increasing Dry Matter Accumulation and Reducing Seed Shattering Under Rainfed Conditions - Muhammad Zeeshan Mehmood; Ghulam Qadir; Obaid Afzal; Atta Mohi Ud Din; Muhammad Ali Raza; Imran Khan; Muhammad Jawad Hassan; Samrah Afzal Awan; Shakeel Ahmad; Muhammad Ansar; Muhammad Aqeel Aslam; Mukhtar Ahmed (International Journal of Plant Production, 2021)
Several biotic and abiotic stresses significantly decrease the biomass accumulation and seed yield of sesame crops under rainfed areas. However, plant growth regulators (such as Paclobutrazol) can improve the total dry matter and seed production of the sesame crop. The effects of the paclobutrazol application on dry matter accumulation and seed yield had not been studied before in sesame under rainfed conditions. Therefore, a two-year field study during 2018 and 2019 was conducted with key objectives to assess the impacts of paclobutrazol on leaf greenness, leaf area, total dry matter production and partitioning, seed shattering, and seed yield of sesame. Two sesame cultivars (TS-5 and TS-3) were treated with four paclobutrazol concentrations (P0 = Control, P1 = 100 mg L −1 , P2 = 200 mg L −1 , P3 = 300 mg L −1 ). The experiment was executed in RCBD-factorial design with three replications. Compared with P0, treatment P3 improved the leaf greenness of sesame by 17%, 38%, and 60% at 45, 85, and 125 days after sowing, respectively. However, P3 treatment decreased the leaf area of sesame by 14% and 20% at 45 and 85 days after sowing than P0, respectively. Compared with P0, treatment P3 increased the leaf area by 46% at 125 days after sowing. On average, treatment P3 also improved the total biomass production by 21% and partitioning in roots, stems, leaves, capsules, and seeds by 23%, 19%, 23%, 22%, and 40%, respectively, in the whole growing seasons as compared to P0. Moreover, under P3 treatment, sesame attained the highest seed yield and lowest seed shattering by 27% and 30%, respectively, compared to P0. This study indicated that by applying the paclobutrazol concentration at the rate of 300 mg L −1 in sesame, the leaf greenness, leaf areas, biomass accumulation, partitioning, seed yield, and shatter resistance could be improved. Thus, the optimum paclobutrazol level could enhance the dry matter accumulation and seed production capacity of sesame by decreasing shattering losses under rainfed conditions.

The nexus between meteorological parameters and COVID-19 pandemic: case of Islamabad, Pakistan - Abdul Rehman; Fatima Ashraf; Zeeshan Javed; Mudassar Hussain; Taimoor Hassan Farooq; Awais Shakoor; Sher Muhammad Shahzad (Environmental Sustainability, 2021)

Adoption of green banking practices and environmental performance in Pakistan: a demonstration of structural equation modelling - Alam Rehman; Irfan Ullah; Fakhr-e-Alam Afridi; Zain Ullah; Muhammad Zeeshan; Arif Hussain; Haseeb Ur Rahman (Environment, Development and Sustainability, 2021)

Greenwash and green purchase behavior: an environmentally sustainable perspective - Irfan Hameed; Zeeshan Hyder; Muhammad Imran; Kashif Shafiq (Environment, Development and Sustainability, 2021)

The glutathione S-transferase (PxGST2L) may contribute to the detoxification metabolism of chlorantraniliprole in Plutella xylostella(L.) - Fei Yin; Qingsheng Lin; Xiaoxiang Wang; Zhenyu Li; Xia Feng; Muhammad Zeeshan Shabbir (Ecotoxicology, 2021)
The diamondback moth ( Plutella xylostella L.), is an economic pest of cruciferous plants worldwide, which causes great economic loss to cruciferous plants production. However, the pest has developed resistance to insecticides. One of such insecticides is chlorantraniliprole. The study of the mechanisms underlying resistance is key for the effective management of resistance. In this study, a comparative proteomics approach was used to isolate and identify various proteins that differed between chlorantraniliprole-susceptible and -resistant strains of P. xylostella . Eleven proteins were significantly different and were successfully identified by MALDI-TOF-MS. Metabolism-related proteins accounted for the highest proportion among the eleven different proteins. The function of the PxGST2L protein was validated by RNAi. Knockdown of PxGST2L reduced the GST activity and increased the toxicity of chlorantraniliprole to the diamondback moth. The resistance ratio of diamondback moth to chlorantraniliprole was reduced from 1029 to 505. The results indicated that PxGST2L is partly responsible for chlorantraniliprole insecticide resistance in DBM. Our finding contributes to the understanding of the mechanism underlying resistance to chlorantraniliprole in the DBM, to develop effective resistance management tactics.

A blessing in disguise?: Assessing the impact of 2010–2011 floods on trust in Pakistan* - Noman Ahmad; Muhammad Zeeshan Younas (Environmental Science and Pollution Research, 2021)

Elucidation of larvicidal potential of metallic and environment friendly food-grade nanostructures against Aedes albopictus - Toqeer Ahmed; Irfan Liaqat; Muhammad Zeeshan Hyder; Shaheen Akhtar; Assad Hafeez Bhatti; Shahid Bilal Butt; Zahid Imran; Tayyaba Yasmin; Shabbar Abbas (Environmental Geochemistry and Health, 2021)

Can sulphur improve the nutrient uptake, partitioning, and seed yield of sesame? - Muhammad Zeeshan Mehmood; Obaid Afzal; Mukhtar Ahmed; Ghulam Qadir; Ahmed M.S. Kheir; Muhammad Aqeel Aslam; Atta Mohi Ud Din; Imran Khan; Muhammad Jawad Hassan; Tehseen Ahmad Meraj; Muhammad Ali Raza; Shakeel Ahmad (Arabian Journal of Geosciences, 2021)
Sulphur (S) is considered to improve the nutrient uptake of plants due to its synergistic relationship with other nutrients. This could ultimately enhance the seed yield of oilseed crops. However, there is limited quantitative information on nutrient uptake, distribution, and its associated impacts on seed yield of sesame under the S application. Thus, a two-year field study (2018 and 2019) was conducted to assess the impacts of different S treatments (S 0 = Control, S 20 = 20, S 40 = 40, and S 60 = 60 kg ha −1 ) on total dry matter production, nitrogen, phosphorus, potassium, S uptake and distribution at the mid-bloom stage and physiological maturity. Furthermore, treatment impacts were studied on the number of capsules per plant, number of seeds per capsule, thousand seed weight, and seed yield at physiological maturity in sesame. Compared to S 0 , over the years, treatment S 40 significantly increased the total uptake of nitrogen, phosphorus, potassium, and S (by 13, 22, 11% and 16%, respectively) at physiological maturity, while their distribution by 13, 36, 14, and 24% (in leaves), 12, 15, 11, and 15% (in stems), 15, 42, 18, and 10% (in capsules), and 14, 22, 9, and 15% (in seeds), respectively. Enhanced nutrient uptake and distribution in treatment S 40 improved the total biomass accumulation (by 28%) and distribution in leaves (by 34%), stems (by 27%), capsules (by 26%), and seeds (by 28%), at physiological maturity, as compared to S 0 . Treatment S 40 increased the number of capsules per plant (by 13%), number of seeds per capsule (by 11%), and thousand seed weight (by 6%), compared to S 0 . Furthermore, over the years, relative to control, sesame under S 40 had a higher seed yield by 28% and enhanced the net economic returns by 44%. Thus, our results suggest that optimum S level at the time of sowing improves the nutrient uptake and distribution during the plant lifecycle, which ultimately enhances total dry matter accumulation, seed yield, and net productivity of sesame.

A research on conventional and modern algorithms for maximum power extraction from wind energy conversion system: a review - Muhammad Zeeshan Malik; Mazhar Hussain Baloch; Mehr Gul; Ghulam Sarwar Kaloi; Sohaib Tahir Chauhdary; Ali Asghar Memon (Environmental Science and Pollution Research, 2021)

Examining the asymmetric effects of Pakistan’s fiscal decentralization on economic growth and environmental quality - Xiaolong Li; Muhammad Zeeshan Younas; Zubaria Andlib; Sana Ullah; Sidra Sohail; Muhammad Hafeez (Environmental Science and Pollution Research, 2021)

Antibiofilm Effects of Macrolide Loaded Microneedle Patches: Prospects in Healing Infected Wounds - Muhammad Sohail Arshad; Aleema Tehreem Zahra; Saman Zafar; Hussain Zaman; Ambreen Akhtar; Muhammad Mazhar Ayaz; Israfil Kucuk; Mohammed Maniruzzaman; Ming-Wei Chang; Zeeshan Ahmad (Pharmaceutical Research, 2021)

Solar still desalination system equipped with paraffin as phase change material: exergoeconomic analysis and multi-objective optimization - Muhammad Zeeshan Malik; Farayi Musharavati; Saber Khanmohammadi; Shoaib Khanmohammadi; Dinh Duc Nguyen (Environmental Science and Pollution Research, 2021)

Influence of indigenous plant materials on reproductive performance of Callosobruchus chinensis (L.) (Coleoptera: Bruchidae) on chickpea - Bilawal Nizamani; Mushtaque Ahmed Agha; Qurban Ali; Amjad Hussain; Hakim Manghwar; Muhammad Kamran; Aafaque Ahmed Keerio; Zeeshan Ahmed Solangi; Muhammad Akbar Lashari; Din Muhammad Soomro (International Journal of Tropical Insect Science, 2020)

Mapping and predicting subsidence from spatio-temporal regression models of groundwater-drawdown and subsidence observations - Muhammad Zeeshan Ali; Hone-Jay Chu; Thomas J. Burbey (Hydrogeology Journal, 2020)

Effect of increasing pre-pubertal concentrate levels on reproductive and lactation performance of Nili-Ravi Buffalo heifers - Muhammad Saadullah; Zeeshan Muhammad Iqbal; Muhammad Naveed-ul-Haque; Hifzulrahman; Jalees Ahmed Bhatti; Muhammad Abdullah (Tropical Animal Health and Production, 2020)

First report of brown leaf spot of rice caused by Curvularia spicifera in Pakistan - Hafiz Muhammad Usman Aslam; Safdar Ali; Muhammad Atiq; Muhammad Zeeshan Mansha; Hafiz Muhammad Aatif; Hafiz Arslan Anwaar; Khalid Naveed (Journal of Plant Pathology, 2020)

Assessment of antibiotics use for children upper respiratory tract infections: a retrospective, cross-sectional study from Pakistan - Zia Ul Mustafa; Muhammad Salman; Alina Zeeshan Rao; Noman Asif; Sanan Amjad Butt; Naureen Shehzadi; Khalid Hussain (Infectious Diseases, 2020)

Inanimate surfaces as potential source of 2019-nCoV spread and their disinfection with biocidal agents - Muhammad Zeeshan Akram (VirusDisease, 2020)

Asymmetric effects of energy efficiency and renewable energy on carbon emissions of BRICS economies: evidence from nonlinear panel autoregressive distributed lag model - Rabia Akram; Muhammad Tariq Majeed; Zeeshan Fareed; Fahad Khalid; Chengang Ye (Environmental Science and Pollution Research, 2020)

The effects of deforestation and urbanization on sustainable growth in Asian countries - Zeeshan Arshad; Margarita Robaina; Muhammad Shahbaz; Anabela Botelho Veloso (Environmental Science and Pollution Research, 2020)

The potential applications of picotechnology in biomedical and environmental sciences - Muhammad Zeeshan Qasim; Hafiz Mohkum Hammad; Farhat Abbas; Shafqat Saeed; Hafiz Faiq Bakhat; Wajid Nasim; Wajid Farhad; Faiz Rabbani; Shah Fahad (Environmental Science and Pollution Research, 2020)

Improved transdermal delivery of cetirizine hydrochloride using polymeric microneedles - Muhammad Sohail Arshad; Sana Hassan; Amjad Hussain; Nasir Abbas; Israfil Kucuk; Kazem Nazari; Radeyah Ali; Suleman Ramzan; Ali Alqahtani; Eleftherios G. Andriotis; Dimitris G. Fatouros; Ming-Wei Chang; et al. (DARU Journal of Pharmaceutical Sciences, 2019)

Total retail goods consumption, industry structure, urban population growth and pollution intensity: an application of panel data analysis for China - Zeeshan Khan; Muhammad Shahbaz; Manzoor Ahmad; Fazli Rabbi; Yang Siqun (Environmental Science and Pollution Research, 2019)

Ionic cross-linking of cellulose nanofibers: an approach to enhance mechanical stability for dynamic adsorption - Muhammad Muqeet; Umair Ahmed Qureshi; Rasool Bux Mahar; Zeeshan Khatri; Farooq Ahmed; Ick-Soo Kim (Environmental Science and Pollution Research, 2019)

Histo-morphological analysis of rice callus cultures reveals differential regeneration response with varying media combinations - Bushra Ijaz; Cristina Sudiro; Muhammad Zeeshan Hyder; Saad Imran Malik; Sumaira Farrakh; Fiorella Lo Schiavo; Tayyaba Yasmin (In Vitro Cellular & Developmental Biology - Plant, 2019)

RETRACTED ARTICLE: A new cationic palladium(II) dithiocarbamate exhibits anti-inflammatory, analgesic, and antipyretic activities through inhibition of inflammatory mediators in in vivo models - Muhammad Naveed; Shahan Zeb Khan; Sara Zeeshan; Adnan Khan; Bushra Shal; Ayesha Atiq; Hussain Ali; Rahim Ullah; Zia-ur-Rehman; Salman Khan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Characterization of recombinant endo-1,4-β-xylanase of Bacillus halodurans C-125 and rational identification of hot spot amino acid residues responsible for enhancing thermostability by an in-silico approach - Malik Siddique Mahmood; Faiz Rasul; Mahjabeen Saleem; Amber Afroz; Muhammad Faheem Malik; Naeem Mehmood Ashraf; Umar Rashid; Shumaila Naz; Nadia Zeeshan (Molecular Biology Reports, 2019)

N-Pyrazoloyl and N-thiopheneacetyl hydrazone of isatin exhibited potent anti-inflammatory and anti-nociceptive properties through suppression of NF-κB, MAPK and oxidative stress signaling in animal models of inflammation - Sara Zeeshan; Muhammad Naveed; Adnan Khan; Ayesha Atiq; Maryam Arif; Muhammad Naeem Ahmed; Yeong Shik Kim; Salman Khan (Inflammation Research, 2019)

The effect of financial development on ecological footprint in BRI countries: evidence from panel data estimation - Muhammad Awais Baloch; Jianjun Zhang; Kashif Iqbal; Zeeshan Iqbal (Environmental Science and Pollution Research, 2019)

Cadmium (Cd) concentration in wheat (Triticum aestivum) grown in Cd-spiked soil varies with the doses and biochar feedstock - Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Muhammad Irfan Sohail; Amjad Hussain; Muhammad Farooq Qayyum; Hinnan Khalid; Muhammad Zeeshan; Naveeda Majid (Arabian Journal of Geosciences, 2018)

Impact of drought on assimilates partitioning associated fruiting physiognomies and yield quality attributes of desert grown cotton - Muhammad Shareef; Dongwei Gui; Fanjiang Zeng; Zeeshan Ahmed; Muhammad Waqas; Bo Zhang; Hassan Iqbal; Muhammad Fiaz (Acta Physiologiae Plantarum, 2018)

Removal of lead from aqueous solution using polyacrylonitrile/magnetite nanofibers - Hammad Malik; Umair Ahmed Qureshi; Muhammad Muqeet; Rasool Bux Mahar; Farooq Ahmed; Zeeshan Khatri (Environmental Science and Pollution Research, 2018)

Effect of Fixed Media Surface Area on Biofouling and Nutrients Removal in Fixed Film Membrane Bioreactor Treating Sewage at Medium and High Fluxes - Muhammad Zeeshan; Sajjad Haydar; Shamas Tabraiz (Water, Air, & Soil Pollution, 2017)

Molecular genetic analysis of consanguineous families with primary microcephaly identified pathogenic variants in the ASPM gene - MUZAMMIL AHMAD KHAN; CHRISTIAN WINDPASSINGER; MUHAMMAD ZEESHAN ALI; MUHAMMAD ZUBAIR; HADIA GUL; SAFDAR ABBAS; SAADULLAH KHAN; MUHAMMAD BADAR; RAMZI M. MOHAMMAD; ZAFAR NAWAZ (Journal of Genetics, 2017)

Evaluating the impact of classification algorithms and spatial resolution on the accuracy of land cover mapping in a mountain environment in Pakistan - Sami Ullah; Muhammad Shafique; Muhammad Farooq; Muhammad Zeeshan; Matthias Dees (Arabian Journal of Geosciences, 2017)

Dynamic linkages among energy consumption, air pollution, greenhouse gas emissions and agricultural production in Pakistan: sustainable agriculture key to policy success - Muhammad Imran Qureshi; Usama Awan; Zeeshan Arshad; Amran Md. Rasli; Khalid Zaman; Faisal Khan (Natural Hazards, 2016)

Characterization of N2O emission and associated bacterial communities from the gut of wood-feeding termite Nasutitermes voeltzkowi - Muhammad Zeeshan Majeed; Edouard Miambi; Muhammad Asam Riaz; Alain Brauman (Folia Microbiologica, 2015)

Structural styles, hydrocarbon prospects, and potential in the Salt Range and Potwar Plateau, north Pakistan - Ishtiaq A. K. Jadoon; Matthias Hinderer; Beenish Wazir; Rizwan Yousaf; Sher Bahadar; Muhammad Hassan; Zeeshan-ul-Hassan Abbasi; Sidra Jadoon (Arabian Journal of Geosciences, 2015)

O-GlcNAc modification of the anti-malarial vaccine candidate PfAMA1: in silico-defined structural changes and potential to generate a better vaccine - Nasir Uddin; Daniel C. Hoessli; Asma Butt; Afshan Kaleem; Zeeshan Iqbal; Imran Afzal; Muhammad Hammad; Zahra Zamani; Abdul Rauf Shakoori (Molecular Biology Reports, 2012)